Cathode diffusion layer for organic hydride production

The use of carbon foam with a specific porous structure in the cathode diffusion layer addresses mass transfer resistance issues in electrolytic synthesis of organic hydrides, enhancing current efficiency and reducing energy losses.

JP7603817B2Active Publication Date: 2024-12-20ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023535203
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-13
Filing Date
2022-06-23
Publication Date
2024-12-20
Estimated Expiration
2042-06-23

AI Technical Summary

Technical Problem

Existing electrolytic synthesis of organic hydrides faces inefficiencies due to mass transfer resistance and side reactions at high current densities, leading to decreased current efficiency and increased energy costs.

Method used

A cathode diffusion layer using carbon foam with a specific porous structure, characterized by continuous voids, linear portions, and bonding portions, reduces mass transfer resistance and enhances current flow even at high current densities.

Benefits of technology

The carbon foam cathode diffusion layer improves current efficiency and electrolytic cell performance by facilitating rapid and uniform supply and discharge of organic compounds, reducing side reactions and energy losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603817000007
    Figure 0007603817000007
  • Figure 0007603817000008
    Figure 0007603817000008
  • Figure 0007603817000009
    Figure 0007603817000009
Patent Text Reader

Abstract

A cathode diffusion layer for the production of an organic hydride according to the present invention is characterized by being a porous body having continuous voids and including a carbon foam having linear parts and binding parts that are bound to the linear parts.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a technique for electrochemically hydrogenating an organic compound, and more particularly to a cathode diffusion layer and a method for producing an electrolysis cell for producing an organic hydride using the cathode diffusion layer. [Background technology]

[0002] Hydrogen is widely used industrially, including in petroleum refining, chemical synthesis materials, metal refining, and stationary fuel cells. In recent years, the possibility of using hydrogen in hydrogen stations for fuel cell vehicles (FCVs), smart communities, hydrogen power plants, and other areas is expanding. Furthermore, as the introduction of renewable energy progresses, it has become necessary to maintain the supply and demand balance in the power grid, and therefore hydrogen carrier technology that can efficiently store and transport large amounts of electricity is being developed.

[0003] Hydrogen carriers include liquefied hydrogen, ammonia, and hydrogenated organic compounds in which hydrogen is chemically bonded to organic compounds such as benzene, toluene, and naphthalene. Liquefied hydrogen has the advantage of having a high hydrogen compression density, but requires low temperatures and high pressures for storage and transportation, and the reduced energy efficiency due to boil-off increases costs. Ammonia can store hydrogen at a higher density than liquefied hydrogen, but the establishment of dehydrogenation technology and handling methods to remove the hydrogen for use are major challenges. On the other hand, methylcyclohexane, a type of hydrogenated organic compound in which hydrogen is bonded to toluene, has the advantage of being able to store hydrogen at a higher density than compressed hydrogen and being able to use the same infrastructure technology as gasoline, although it is inferior to liquefied hydrogen and ammonia. In addition, dehydrogenation catalysts have been developed, and methylcyclohexane is considered to be the most feasible hydrogen carrier.

[0004] Hydrogenated organic compounds as hydrogen carriers are produced by injecting hydrogen and the gas of the organic compound to be hydrogenated under high temperature and pressure conditions into a fixed-bed reactor in which a granular catalyst is supported on a mesh bed. However, the hydrogenation reaction of the organic compound to be hydrogenated, such as benzene and toluene, is an exothermic reaction, so part of the energy of the hydrogen is lost as heat. In addition, in order to extract hydrogen from the hydrogenated organic compound, the energy equivalent to this heat loss must be re-input, which raises the issue of high energy costs required for hydrogen utilization.

[0005] Meanwhile, a technology has been developed that produces hydrogenated organic compounds directly, without going through hydrogen, by electrochemically reacting water with the organic compounds to be hydrogenated. This method can reduce the heat loss caused by the hydrogenation reaction, and also makes a hydrogenation plant unnecessary, allowing for a significant reduction in equipment. As a result, it is expected that the total cost of using hydrogen will be reduced.

[0006] Patent documents 1 to 5 report methods for producing hydrogenated organic compounds using an electrochemical reduction device having a solid polymer electrolyte (PEM) type electrolytic synthesis cell having a structure similar to that of a fuel cell. Patent document 6 discloses a redox flow battery using carbon foam for the electrodes. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2003-45449 A [Patent Document 2] JP 2005-126288 A [Patent Document 3] JP 2013-111585 A [Patent Document 4] International Publication No. 2015 / 029367 [Patent Document 5] International Publication No. 2015 / 146944 [Patent Document 6] International Publication No. 2020 / 184455 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the above technology has some points to be improved in terms of electrolysis efficiency. In the electrolysis of organic hydrides, the anode chamber liquid, which is an aqueous solution, and the cathode chamber liquid, which is an organic compound, are separated by a PEM membrane. On the electrode surface of the cathode chamber, it is necessary to supply the raw material, the organic compound to be hydrogenated, and discharge the product, the hydrogenated organic compound, quickly and uniformly. If the supply and discharge are not performed quickly, it leads to hydrogen generation due to a side reaction, which hinders the reduction of the target toluene, and causes a decrease in current efficiency. From this perspective, if the temperature of the organic hydride electrolysis cell is increased, the viscosity of the toluene, which is the organic compound to be hydrogenated, decreases and the mass transfer of toluene is improved, while the amount of water that permeates the PEM membrane from the anode chamber and diffuses to the cathode chamber increases, hindering the mass transfer of toluene. As a result, the current efficiency, which is the efficiency of the number of electrons that contributed to the purification of the hydrogenated organic compound relative to the number of electrons passed through the electrolysis cell, decreases. This tendency is more pronounced when the current density increases. To further improve the current efficiency, improvement of the mass transfer of toluene is highly desirable.

[0009] Patent Document 6 discloses a redox flow battery that is charged and discharged by passing an aqueous electrolyte solution through a carbon foam electrode and exchanging electrons with an active material on the electrode surface, but does not mention mass transfer.

[0010] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and has an object to provide a cathode diffusion layer for organic hydride production, which exhibits good current efficiency even at high current densities, by improving the mass transfer resistance on the cathode chamber side, and an electrolytic cell for organic hydride production. [Means for solving the problem]

[0011] As a result of extensive investigations into ways to solve the above problems, the inventors discovered that the use of a carbon foam having a specific porous structure in the cathode diffusion layer reduces mass transfer resistance and exhibits good current efficiency even at high current densities, thereby completing the present invention.

[0012] That is, the present invention is as follows. [1] A porous body having continuous voids, comprising linear portions and connecting portions that connect the linear portions, and the average fiber diameter of the linear portions is 0.5 μm or more and 4.0 μm or less. The average carbon frequency is 0.0004 to 0.0035 μm. -2 is A cathode diffusion layer for organic hydride production, comprising a carbon foam. [2] The cathode diffusion layer for organic hydride production according to [1], wherein the carbon foam has a Taber stiffness of 1.0 to 50.0 gf·cm as measured in accordance with JIS P8125. [3] The carbon foam has a density of the bonds of 20,000 bonds / mm 3 The cathode diffusion layer for producing an organic hydride according to [1] or [2], wherein the crystallite size is 1.50 nm or more based on diffraction of the (002) plane in powder X-ray diffraction measurement. [4 ] before The carbon form has a standard deviation of carbon frequency of 0.0005 or less,[1]~[ 3 13. The cathode diffusion layer for producing an organic hydride according to any one of claims 1 to 12. [ 5 ] The carbon foam has an average carbon area ratio of 0.010 to 0.300, [1] to [ 4 13. The cathode diffusion layer for producing an organic hydride according to any one of claims 1 to 12. [ 6 ] The carbon foam has a standard deviation of the carbon area ratio of 0.030 or less, [1] to [ 5 13. The cathode diffusion layer for producing an organic hydride according to any one of claims 1 to 12. [7 ] A proton-conductive solid polymer electrolyte membrane, an anode catalyst layer that oxidizes water to generate protons provided on one side of the solid polymer electrolyte membrane, and a cathode catalyst layer that reduces a substance to be hydrogenated provided on the other side of the solid polymer electrolyte membrane, and 6 13. An electrolysis cell for producing organic hydride, comprising the cathode diffusion layer according to any one of claims 1 to 12. 。 [8 ] the solid polymer electrolyte membrane is a perfluorocarbon polymer having an ion exchange group, the equivalent mass EW of the ion exchange group is 600 g / eq or more and 2000 g / eq or less, and in the dimensional change rate due to immersion in distilled water described below, at least one of the dimensional change rate in the X direction and the Y direction is 80% or more and less than 100%, the dimensional change rate in the Z direction is 115% or more, and the ion cluster diameter in the direction perpendicular to the membrane surface measured by small angle X-ray scattering is 3.0 nm or more, [ 7 ] An electrolytic cell for producing organic hydride according to the present invention. <Dimensional change rate due to immersion in distilled water> A test electrolyte membrane having a water content of 1% or less is prepared, and the test electrolyte membrane is immersed in distilled water at 25°C for 30 minutes. The dimensional change rates of the test electrolyte membrane in the X direction, the Y direction perpendicular to the X direction, and the Z direction perpendicular to the X direction and the Y direction are calculated. Dimensional change rate (%) = (dimension in a specific direction after immersion) / (dimension in a specific direction before immersion) x 100 [ 9 ] The solid polymer electrolyte membrane has a peak intensity of a crystal long period of 0.5 or less as measured by small angle X-ray scattering; 7 ] or [8] 2. An electrolytic cell for producing organic hydride according to claim 1 . [ 10 ] The solid polymer electrolyte membrane has a craze area ratio of 1.5% or less, 7 ]~[ 9

[0023] The electrolytic cell for producing organic hydride according to any one of the preceding claims. 。 Effect of the Invention

[0013] According to the present invention, it is possible to provide a cathode diffusion layer for producing an organic hydride, which exhibits good current efficiency even at a high current density, and an electrolytic cell for producing an organic hydride. [Brief description of the drawings]

[0014] [Figure 1] 1 is a SEM image of an example of a carbon foam with interconnected porosity. [Diagram 2] 1 is a flow chart of a method for making carbon foam according to the present embodiments. [Diagram 3] 1 is an SEM image of the carbon foam used in Example 1. [Figure 4] 1 is an SEM image of the carbon foam used in Comparative Example 3. [Diagram 5] 13 is an analysis image showing the carbon frequency of the carbon foam used in Example 3. [Figure 6] 1 is a graph showing the carbon frequency per 1 μm2 in the thickness direction of the carbon foam used in Example 3 and Reference Example 11, the carbon fiber paper used in Reference Example 13, and the carbon fiber nonwoven fabric used in Comparative Example 2. [Figure 7] 1 is a graph showing the carbon area ratio in the thickness direction of the carbon foams used in Example 3 and Reference Example 11, the carbon fiber paper used in Reference Example 13, and the carbon fiber nonwoven fabric used in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Below, we will explain in detail the form for implementing the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to the following description and can be implemented in various modifications within the scope of its gist.

[0016] The organic hydride producing apparatus of this embodiment for producing an organic hydride comprises a proton-conductive polymer electrolyte membrane, an anode catalyst provided on one side of the solid polymer electrolyte membrane for oxidizing water to generate protons, and a cathode catalyst layer provided on the other side of the solid polymer electrolyte membrane for reducing the substance to be hydrided, and separates an anode chamber for supplying water from a cathode chamber for supplying the substance to be hydrided. The cathode diffusion layer is provided in the cathode chamber and adjacent to the cathode catalyst, and serves to supply the substance to be hydrided and discharge the hydride, as well as to act as a conductor of electrons used in the reduction.

[0017] From the viewpoint of efficiently conducting electrons from the current collector to the catalyst layer, the cathode diffusion layer of this embodiment preferably has a structure in which conductors are three-dimensionally continuous. From the viewpoint of rapid mass transfer between the material to be hydrided and the hydride, it is preferable that the material is a porous material having continuous pores. From these viewpoints, carbon foam is preferably used. FIG. 1 is an SEM image of an example of a carbon foam with interconnected pores.

[0018] The carbon foam of this embodiment preferably has linear portions and connecting portions that connect the linear portions. A plurality of linear portions (two or more, three or more, four or more, etc.) may be connected to one connecting portion. In the present invention, the fiber diameter of the linear portion is the thickness of the linear portion that connects the connecting portions. Of the portions having a linear shape, the range in which the fiber diameter is within twice the minimum fiber diameter of the portion is defined as the linear portion, and the range in which the fiber diameter is more than twice the minimum fiber diameter of the portion is defined as the connecting portion.

[0019] (Average fiber diameter of linear part) From the viewpoint of good physical strength and electrical conductivity, the average fiber diameter of the linear portion in the carbon foam of this embodiment is preferably 0.5 μm or more, more preferably 0.8 μm or more, and most preferably 1.2 μm or more. Also, from the viewpoint of good deformability and recovery property during compression behavior of the carbon foam, the average fiber diameter of the linear portion is preferably 4.0 μm or less, more preferably 3.5 μm or less, and most preferably 3.0 μm or less.

[0020] (joint density) The density of the bonded portion of the carbon foam of this embodiment is set to 20,000 pieces / mm from the viewpoint of restoring property when a compressive load is applied. 3 More preferably, it is 80,000 pieces / mm 3 More preferably, 500,000 pieces / mm 3 The density of the bonded parts of the carbon foam is set at 5,000,000 pieces / mm from the viewpoint of flexibility of the carbon foam. 3 It is preferable that the number of particles is less than 4,000,000 / mm 3 or less, and more preferably 3,000,000 pieces / mm 3 The following is the result.

[0021] It is preferable that at least a portion of the carbon foam of this embodiment has a bond that meets the above density range, it is more preferable that 50% by volume of the bond meets the above density range, it is even more preferable that 75% by volume of the bond meets the above density range, and it is particularly preferable that any portion of the carbon foam meets the above density range.

[0022] (Surface functional group concentration) In the carbon foam of this embodiment, the ratio of graphite among the carbon atoms measured by X-ray photoelectron spectroscopy is preferably 70 at% or more. When the ratio is 70 at% or more, the resistance can be stably maintained low for long-term charge and discharge in a configuration in which the carbon foam is used in a cathode diffusion layer. Furthermore, alternatively or additionally, in the carbon foam of this embodiment, the total ratio of carbon atoms having a hydroxyl group, carbon atoms constituting a carbonyl group, and carbon atoms constituting a carboxyl group among the carbon atoms measured by X-ray photoelectron spectroscopy is preferably 40 at% or less, more preferably 20 at% or less, and preferably 10 at% or less, from the viewpoint of improving the affinity with the substance to be hydrogenated and improving the discharge of water permeating through the solid polymer electrolyte membrane.

[0023] (carbon content) From the viewpoint of electrical conductivity, the carbon content of the carbon foam of this embodiment is preferably 51% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, more preferably 85% by mass or more, more preferably 90% by mass or more, and even more preferably 98% by mass or more. The upper limit of the carbon content is not particularly limited, but may be 100% by mass or less, or may be 99% by mass or less. The carbon content of the carbon foam can be determined by fluorescent X-ray measurement, and specifically, the carbon content is measured by the method described in the examples.

[0024] (Ratio of number of linear parts to number of bonded parts) In the carbon foam of this embodiment, the ratio of the number of linear portions to the number of bonding portions may be 1.4 or more and 1.55 or less. In other words, the ratio is the average number of branches branched at the bonding portions. When the ratio is 1.4 or more, a structure in which linear portions do not have a three-dimensional mesh structure bonded at bonding portions and unbonded linear portions are in contact with each other, such as a nonwoven fabric, can be excluded from the carbon foam of this embodiment. Also, when the ratio is 1.55 or less, a porous structure in which the linear portions are strip-like and are covered with walls like a honeycomb can be excluded from the carbon foam of this embodiment. The ratio is preferably 1.42 or more and 1.53 or less, more preferably 1.44 or more and 1.50 or less.

[0025] (Orientation angle of linear part) When, for example, melamine resin foam is heat-treated and carbonized in a heat treatment furnace, the carbon foam has an isotropic structure in which the carbon fibers constituting the skeleton of the carbon foam are spread evenly in all directions. In such carbon foam, the difference θ between the average orientation angle of the linear portion in one direction and the average orientation angle in the other directions among the three mutually orthogonal directions is usually 1° or less. However, when a compressive stress is applied to the resin foam, which is the raw material of the carbon foam, during the heat treatment and carbonization of the melamine resin foam, a carbon foam having a skeletal structure in which the carbon fibers have anisotropic expansion is obtained. In such a carbon foam, even when a compressive load is applied, breakage of the carbon fibers (linear parts) can be suppressed, powder falling can be reduced, and high restorability can be achieved. To achieve this effect, in the carbon foam of this embodiment, the difference in the average values ​​of the orientation angles may be 3° or more. The difference is preferably 5° or more, and more preferably 8° or more. The above three directions may be, for example, the x, y, and z directions, and may be arbitrarily set for the carbon foam.

[0026] (porosity) The porosity of the carbon foam of this embodiment may be 50% or more, preferably 60% or more, and more preferably 70% or more, from the viewpoint of flexibility, and may be 99% or less, preferably 98% or less, and more preferably 95% or less, from the viewpoint of improving the surface area and reducing the cell resistance.

[0027] In this embodiment, the porosity is a value calculated from the bulk density and the true density. The bulk density is a density based on the volume including the voids contained in the carbon foam. In contrast, the true density is a density based on the volume occupied by the carbon foam material.

[0028] (Taper bending stiffness) From the viewpoint of easy handling, the carbon foam of this embodiment preferably has a Taber flexural rigidity measured according to JIS P8125 of 1.0 gf·cm or more, more preferably 5.0 gf·cm or more, and most preferably 10.0 gf·cm or more. On the other hand, from the viewpoint of high flexibility and good conformability inside the cells, it is preferably 50.0 gf·cm or less, more preferably 45.0 gf·cm or less, and most preferably 40.0 gf·cm or less. The Taber flexural rigidity of the carbon foam can be increased, for example, by compressing the carbon foam during the process of forming it to adjust the density to a high level, or by coating the surface of the carbon foam with a carbon material such as carbon black.

[0029] (Crystallite size) The crystallite size Lc of the carbon foam of this embodiment is preferably 1.50 nm or more, more preferably 1.80 nm or more from the viewpoint of electrical conductivity, and is preferably 4.00 nm or less, more preferably 3.00 nm or less from the viewpoint of physical fragility.

[0030] (average carbon frequency) The average carbon frequency of the carbon foam of this embodiment is preferably 0.0004 or more, more preferably 0.0005 or more, and even more preferably 0.0010 or more, from the viewpoint of ensuring good contact with the cathode catalyst layer and the current collector plate (cathode plate) and reducing resistance. Also, from the viewpoint of maintaining the strength in the cathode diffusion layer and ensuring flexibility, thereby improving handleability, the average carbon frequency is preferably 0.0035 or less, more preferably 0.0030 or less, and even more preferably 0.0028 or less.

[0031] (Average carbon area ratio) The average carbon area ratio of the carbon foam of this embodiment is preferably 0.010 or more, more preferably 0.020 or more, and even more preferably 0.10 or more, from the viewpoint of improving the electrical conductivity of the cathode diffusion layer. Also, from the viewpoint of ensuring the liquid permeability in the cathode diffusion layer and reducing the resistance in the mass transfer, the average carbon area ratio is preferably 0.300 or less, more preferably 0.250 or less, and even more preferably 0.200 or less.

[0032] (Standard deviation of carbon frequency) The standard deviation of the carbon frequency of the carbon foam of this embodiment is preferably 0.0005 or less, more preferably 0.0004 or less, and even more preferably 0.0002 or less, from the viewpoints of uniform liquid permeability in the cathode diffusion layer, efficient hydrogenation reaction, and good current efficiency. The lower limit of the standard deviation of the carbon frequency is not particularly limited.

[0033] (Standard deviation of carbon area ratio) The standard deviation of the carbon area ratio of the carbon foam of this embodiment is preferably 0.030 or less, more preferably 0.025 or less, and even more preferably 0.020 or less, from the viewpoints of uniform liquid permeability in the cathode diffusion layer, efficient hydrogenation reaction, and good current efficiency. The lower limit of the standard deviation of the carbon area ratio is not particularly limited.

[0034] (Method of measuring crystallite size) The crystallite size Lc is evaluated from the diffraction of the (002) plane of the carbon foam. After crushing the sample in a mortar, wide-angle X-ray measurement of the crushed sample is performed using a tabletop X-ray diffractometer D2 PHASER (manufactured by Bluker). The specific measurement conditions are as follows. -Measurement conditions- Source: Cu Kα Tube current: 30mA Tube voltage: 40kV Slit: 1mm Sample rotation speed: 10 rpm Measurement time for one step: 0.3 sec Starting angle (2θ): 5.00° Measurement step (2θ): 0.01° End angle (2θ): 90.00° After the above measurements, the obtained data is analyzed to calculate the crystallite size Lc. The crystallite size Lc can be calculated by substituting the half-width β of the diffraction peak of the (002) plane that appears near 2θ=25 degrees and the angle θ of the peak maximum value into the following formula (c) (Scherrer's formula). Generally, the higher the temperature at which carbonization is performed, the higher the crystallinity and the larger the Lc value. Lc = (Kλ) / βcosθ (c) Here, K is the shape factor and λ is the wavelength of the radiation source. Since the shape factor is the (002) plane diffraction, substitute 0.90. Since the radiation source used this time is CuKα, substitute 1.541 for the calculation.

[0035] (Method of measuring average fiber diameter) In this specification, the fiber diameter of the carbon fibers constituting the carbon foam is determined by image analysis of a scanning electron microscope (SEM) image. Specifically, the carbon foam is observed at a magnification of 10,000 times using a scanning electron microscope. Assuming that the cross-sectional shape is circular, the thickness of the carbon fiber is regarded as the fiber diameter. The average fiber diameter is the average value of the fiber diameters measured as described above at any 20 points.

[0036] (Method of measuring bond density, number of bond and linear parts, and orientation angle) In this specification, the bond density, the number of bonds and linear portions, and the orientation angle are values ​​obtained by photographing the carbon foam using an X-ray CT (Computerized Tomography) device, passing a 3D Median filter with a filter size of radius 2 pixels through the obtained tomographic image data as preprocessing, and then dividing the data into structural and spatial regions using Otsu's binarization algorithm (see Otsu, Nobuyuki, "Automatic Threshold Selection Method Based on Discrimination and Least Squares Criterion," Institute of Electronics, Information and Communication Engineers, Journal D, Vol. J63-D, No. 4, pp. 346-356 (1980)), creating a 3D image of the structure including the interior of the carbon foam, and then using structural analysis software to determine the values ​​from the obtained 3D image. Specifically, the number of bonds and linear portions is determined by detecting and counting the number of bonds and linear portions contained in the three-dimensional image obtained as described above. The bond density is determined by counting the number of bonds per unit volume of 1 mm x 1 mm x 1 mm. The ratio of the number of linear portions to the number of bonds is determined based on the number of bonds and linear portions counted as described above for the same carbon foam. In addition, the orientation angle θ of the linear portion is the angle between the straight line connecting the joints at both ends of the linear portion and each direction, and is determined for each of three mutually perpendicular directions in the three-dimensional image, and the average orientation angle of the linear portion is determined for each direction. The CT device used for the structural analysis of the carbon foam can be a CT device using low-energy, high-brightness X-rays, such as the high-resolution 3D X-ray microscope nano3DX manufactured by Rigaku Corp. For image processing and structural analysis, for example, the Centerline editor of the software Simpleware manufactured by JSOL Corp. can be used.

[0037] (Method of measuring average carbon frequency and average carbon area ratio) In this specification, the average carbon frequency and average carbon area ratio of the carbon foam are measured as follows. The three-dimensional image obtained using the X-ray CT device is processed with a three-dimensional Median filter with a filter size of 2 pixels in radius, and binarized using Otsu's algorithm. Furthermore, within the analysis region (624 μm × 624 μm) of the cross-sectional image in the thickness direction of the carbon foam (a cross-sectional image cut perpendicular to the thickness direction of the carbon foam), the particle analysis function of the image processing software ImageJ is used to detect the number of continuous carbon parts in the analysis region and the total area of ​​the continuous carbon parts, and the carbon frequency and carbon area ratio per 1 μm × 1 μm can be calculated by dividing the result by the area of ​​the analysis region as shown below. The same operation is repeated for 1152 cross-sectional images in the thickness direction of the carbon foam (obtained at a pitch of 0.54 μm), and the average value of the measured values ​​obtained in the entire region is calculated, thereby obtaining the average carbon frequency and average carbon area ratio. In addition, at the time of analysis, calculations can be performed under analysis conditions that include the edge regions of the image. Furthermore, when calculating the average, in order to exclude areas where no carbon exists as samples, the average is calculated using cross-sectional images in which the carbon area ratio in the analysis area is 0.01 or more. Carbon Frequency (μm -2 ) = Number of continuous carbon parts / Area of ​​analysis region Carbon area ratio = total area of ​​continuous carbon parts / area of ​​analysis region [Image processing conditions] Resolution: 1152 x 1202 pixels Pixel size: 0.54μm / pixel Thickness direction: 1152 sheets (0.54 μm / pitch) Software used: ImageJ 1.50i

[0038] (Method of measuring standard deviation of carbon frequency) The standard deviation of the carbon frequency obtained from each cross-sectional image in the thickness direction of the carbon foam can be calculated for the average carbon frequency described above. In order to exclude areas where carbon does not exist as a sample, cross-sectional images in which the carbon area ratio in the analysis area is 0.01 or more are used.

[0039] (Method for measuring standard deviation of carbon area ratio) Regarding the carbon area ratio of the carbon foam described above, the standard deviation of the carbon area ratio obtained in each cross-sectional image in the thickness direction can be calculated. In this case, in order to exclude the area where no carbon exists as a sample, cross-sectional images in which the carbon area ratio in the analysis area is 0.01 or more are used.

[0040] (Method of measuring surface area) In this specification, the surface area of ​​the carbon foam is determined by measuring the surface dimensions using, for example, a vernier caliper and calculating the surface area from the obtained dimensions.

[0041] (Method for measuring functional group concentration) In this specification, the surface analysis of the carbon foam by X-ray photoelectron spectroscopy is performed as follows. The oxygen-containing functional group concentration on the carbon foam surface can be measured using an X-ray photoelectron spectrometer (PerkinElmer, ESCA-5500MT). The obtained C1s peak is fitted with four Gaussian distributions with peaks at binding energies of 284.4 eV (graphite), 285.6 eV (C-OH), 287.0 eV (C=O), and 288.6 eV (COOH), and the ratio of the area of ​​each peak to the total area of ​​the four peaks is calculated, thereby obtaining each surface functional group concentration. In addition, the total surface functional group concentration can be obtained from the ratio of the total area of ​​the three peaks at binding energies of 285.6 eV (C-OH), 287.0 eV (C=O), and 288.6 eV (COOH) to the total area of ​​the four peaks.

[0042] (Calculation of void ratio) In this specification, the porosity Vf,pore can be calculated from the bulk density ρbulk and the real density ρreal calculated as described below using the following formula (X). Vf,pore=((1 / ρbulk)-(1 / ρreal)) / (1 / ρbulk)×100 (%) ···(X)

[0043] (Measurement of bulk density) First, the dimensions of the carbon foam are measured using a caliper or the like, and the bulk volume Vbulk of the carbon foam is calculated from the obtained dimensions. Next, the mass M of the carbon foam is measured using a precision balance. From the obtained mass M and bulk volume Vbulk, the bulk density ρbulk of the carbon foam can be calculated using the following formula (Y). ρbulk=M / Vbulk (Y)

[0044] (True density measurement) The real density ρreal of the carbon foam can be determined by the sink-float method using a mixture of n-heptane, carbon tetrachloride, and ethylene dibromide. Specifically, first, a carbon foam of an appropriate size is placed in a stoppered test tube. Next, an appropriate mixture of three solvents is added to the test tube, which is then immersed in a thermostatic bath at 30°C. If the test piece floats, n-heptane, which has a low density, is added. On the other hand, if the test piece sinks, ethylene dibromide, which has a high density, is added. This procedure is repeated until the test piece floats in the liquid. Finally, the density of the liquid is measured using a Gay-Lussac pycnometer.

[0045] (Method of manufacturing carbon foam) The method for producing carbon foam of this embodiment may include a raw foam introduction step of introducing a resin foam, which is a raw material for the carbon foam, into a heat treatment furnace, a heating step of raising the temperature in the heat treatment furnace to a heat treatment temperature at a first heating rate, a carbonization step of maintaining the heat treatment temperature for a predetermined time to carbonize the resin foam to obtain a carbon foam, a heating step of lowering the temperature in the heat treatment furnace to room temperature, and a carbon foam removal step of removing the carbon foam from the heat treatment furnace. Here, the heating step may be performed while evacuating the heat treatment furnace under reduced pressure at least in a first temperature range where a large amount of decomposition desorbed gas is generated from the resin foam.

[0046] FIG. 2 is a flow chart of a method for making carbon foam according to the present embodiment.

[0047] First, in step S1, a resin foam that is a raw material for the carbon foam is introduced into a heat treatment furnace.

[0048] (Raw material foam introduction process) As the resin foam as the raw material of the carbon foam, any resin foam known as a raw material for carbon foam can be used. For example, when a melamine resin foam is used as the raw material resin foam, the melamine resin foam can be, for example, a melamine / formaldehyde condensation foam produced by the method disclosed in JP-A-4-349178. Note that the resin foam is not limited to melamine resin foam, and may be a urethane resin foam or a phenolic resin foam. According to the above-mentioned method, first, an aqueous solution or dispersion containing a melamine / formaldehyde precondensate, an emulsifier, a vaporizable blowing agent, a curing agent, and, if necessary, a known filler is foamed, and then cured to obtain a melamine / formaldehyde condensation foam.

[0049] In the above method, the melamine / formaldehyde precondensate may have a melamine:formaldehyde ratio of 1:1.5 to 1:4 and an average molecular weight of 200 to 1000. The emulsifier may be, for example, 0.5 to 5 mass % (based on the melamine / formaldehyde precondensate, the same applies below) of sodium salt of alkylsulfonic acid or arylsulfonic acid. The vaporizable foaming agent may be, for example, 1 to 50 mass % of pentane or hexane. The hardening agent may be, for example, 0.01 to 20 mass % of hydrochloric acid or sulfuric acid. In the foaming and hardening treatments, a solution consisting of the above components may be heated to a temperature set according to the type of vaporizable foaming agent used.

[0050] Furthermore, the heat treatment furnace for carbonizing the raw material resin foam is not limited as long as it is a furnace that can carbonize the resin foam to obtain a carbon foam, and for example, a heat treatment furnace that is equipped with a reaction furnace that contains the raw material resin foam, a heater that heats the inside of the reaction furnace, a gas inlet that introduces an inert gas into the reaction furnace, a gas outlet that exhausts gas from the reaction furnace, and a vacuum pump that reduces the pressure inside the reaction furnace to create a vacuum can be used.

[0051] Next, in step S2, the temperature in the heat treatment furnace is raised to a predetermined heat treatment temperature at a first heating rate (heating step). At that time, it is essential to carry out the heating process while decompressing and evacuating the heat treatment furnace in the first temperature range where a large amount of decomposition gas is generated from the resin foam.

[0052] As described above, when the resin foam, which is the raw material of the carbon foam, is heated, the active decomposable desorbed gas generated from the resin foam reacts with the carbon fibers constituting the carbon foam and decomposes locally, causing heterogeneity in the carbon foam. The amount of decomposable desorbed gas generated depends on the temperature inside the furnace. Therefore, in this embodiment, the heat treatment furnace is evacuated under reduced pressure in a temperature range (first temperature range) in which a large amount of decomposable desorbed gas is generated from the resin foam during the temperature increase process. This promotes the diffusion of the decomposable desorbed gas generated inside the resin foam to the outside of the resin foam, thereby preventing the occurrence of heterogeneity in the carbon foam.

[0053] In this embodiment, the temperature range (first temperature range) in which a large amount of decomposition desorbed gas is generated from the resin foam is determined by monitoring the weight of the raw material resin foam in the temperature raising step in advance at intervals of 100° C. from 0° C., and determining that the weight of the resin foam decreases by 5% or more of the initial weight per 100° C. For example, in all temperature ranges of 300° C. or more and less than 400° C., 400° C. or more and less than 500° C., and 500° C. or more and less than 600° C., if the weight of the resin foam decreases by 5% or more of the initial weight per 100° C., the first temperature range is 300° C. or more and less than 600° C.

[0054] As a result of investigations by the present inventors, it was found that when the resin foam is a melamine resin foam, the temperature range (first temperature range) in which a large amount of decomposition desorbed gas is generated is a temperature range of 200° C. or more and less than 800° C. Therefore, when the resin foam is a melamine resin foam, for example, the inside of the heat treatment furnace is evacuated under reduced pressure at least in the first temperature range.

[0055] The above-mentioned decompression and evacuation can be carried out using an evacuation means such as a vacuum pump, and this is carried out using a pump having an evacuation capacity capable of reducing the pressure inside the furnace to 1 Pa or less within 10 minutes.

[0056] The heating rate (first heating rate) to the heat treatment temperature is preferably 10° C. / min or less from the viewpoint of suppressing the amount of decomposition gas generated when the raw material resin foam is a melamine resin foam, and is preferably 1° C. / min or more from the viewpoint of overall productivity.

[0057] In addition, in the temperature range (first temperature range) where the amount of decomposable desorbed gas generated from the resin foam is large, the temperature increase step is preferably performed at a temperature increase rate (second temperature increase rate) lower than the temperature increase rate (first temperature increase rate) up to the heat treatment temperature. This reduces the amount of decomposable desorbed gas generated per unit time in the resin foam, and further promotes the diffusion of the decomposable desorbed gas outside the foam structure. When the temperature increase rate is reduced in the first temperature range (i.e., when changed to the second temperature increase rate), the temperature increase rate may be returned to the first temperature increase rate after the temperature in the furnace exceeds the upper limit of the first temperature range.

[0058] Furthermore, the temperature increasing step is preferably carried out at a temperature increasing rate (third temperature increasing rate) lower than the second temperature increasing rate in a region (second temperature region) where the increase rate of the amount of decomposable desorbed gas generated is high within the first temperature region where the amount of desorbed gas generated is large, thereby further reducing the amount of decomposable desorbed gas generated per unit time within the resin foam and further promoting the diffusion of the decomposable desorbed gas outside the foam structure.

[0059] In this embodiment, the temperature range (second temperature range) where the rate of increase in the amount of decomposition desorbed gas generated from the resin foam is high may be determined by monitoring the weight of the raw material resin foam in the temperature raising step in advance at intervals of 100° C. from 0° C., and determining the temperature range where the weight of the resin foam decreases by 20% or more of the initial weight per 100° C. For example, in the temperature ranges of 300° C. or more and less than 400° C. and 400° C. or more and less than 500° C., if the weight of the resin foam decreases by 20% or more of the initial weight per 100° C., the second temperature range is 300° C. or more and less than 500° C.

[0060] When the raw material resin foam is a melamine resin foam, the temperature range (first temperature range) in which the amount of gas released from the resin foam is large is a temperature range of 200°C or more and less than 800°C, as described above. Furthermore, as a result of studies by the present inventors, it was found that the temperature range (second temperature range) in which the rate of increase in the amount of gas released from the resin foam is high is a temperature range of 300°C or more and less than 400°C. Therefore, when the raw material resin foam is a melamine resin foam, it is more preferable that the heating rate is 5°C / min or less in the first temperature range, and particularly preferably 3°C / min or less in the second temperature range.

[0061] In addition, in order to prevent a decomposition reaction between oxygen and the carbon fibers that constitute the carbon foam in this heating step and the carbonization step described later, the atmosphere in the furnace may be an inert gas atmosphere or a vacuum. Here, the furnace being a vacuum means that the degree of vacuum in the furnace is less than 1 Pa. In addition, the inert gas atmosphere is created by evacuating the furnace after the resin foam that is the raw material of the carbon foam is introduced into the heat treatment furnace (raw material foam introduction step) and removing the air containing oxygen. Then, after the vacuum degree in the furnace reaches less than 1 Pa and the air is sufficiently degassed, nitrogen gas is introduced. In this way, the furnace can be made into a nitrogen gas atmosphere. After the furnace is made into an inert gas atmosphere or a vacuum in this way, heating is started, and the furnace is evacuated and reduced in pressure in the first temperature region.

[0062] Furthermore, in the region of 200°C or higher and lower than 800°C (first temperature region) where the amount of desorbed gas from the melamine resin foam is large, it is preferable to continue decompression and evacuation while introducing an inert gas into the furnace, which generates a flow of inert gas such as nitrogen gas or argon gas in the furnace and promotes the discharge of desorbed decomposition gas generated in the resin foam.

[0063] When the inert gas is introduced, the flow rate of the inert gas is preferably 1 L / min or more, more preferably 3 L / min or more, and particularly preferably 5 L / min or more, and is preferably 40 L / min or less, more preferably 30 L / min or less, and particularly preferably 20 L / min or less.

[0064] Next, in step S3, the resin foam is carbonized by holding the heat treatment temperature reached by the heating for a predetermined time to obtain a carbon foam (carbonization step). In this embodiment, the heat treatment temperature is a temperature equal to or higher than the softening point of the raw material resin foam. For example, when the resin foam is a melamine resin foam, the softening point of the melamine resin foam is 300°C to 400°C, so the heat treatment temperature is a temperature equal to or higher than the softening point. The heat treatment temperature for the melamine resin foam is preferably 800°C or higher, more preferably 1000°C or higher. In addition, from the viewpoint of physical fragility due to high crystallinity, the heat treatment temperature for the melamine resin foam is preferably 3000°C or lower, more preferably 2500°C or lower.

[0065] The time for which the raw material resin foam is held at the heat treatment temperature (heat treatment time) may be the time required for complete carbonization. For example, when the raw material resin foam is a melamine resin foam, the holding time is 0.5 hours or more. The holding time for the melamine resin foam is preferably 1 hour or more, and more preferably 2 hours or more. From the viewpoint of productivity, the holding time for the melamine resin foam is preferably 5 hours or less, and more preferably 4 hours or less.

[0066] Next, in step S4, the temperature inside the heat treatment furnace is lowered to room temperature (temperature lowering step). The temperature lowering rate during carbonization of the melamine resin foam is preferably 20°C / min or less from the viewpoint of reducing damage to the heater and heat insulating material inside the furnace due to rapid cooling. The temperature lowering rate for the melamine resin foam is more preferably 15°C / min or less. Furthermore, from the viewpoint of overall productivity, the temperature lowering rate for the melamine resin foam is preferably 5°C / min or more. The temperature lowering rate for the melamine resin foam is more preferably 10°C / min or more.

[0067] Finally, in step S5, the carbon foam is removed from the heat treatment furnace (carbon foam removal step). In this manner, the carbon foam according to the present invention described above can be produced.

[0068] In addition, by carrying out the heating step and the carbonization step while applying a compressive load to the raw material resin foam, a carbon foam having a skeletal structure in which the carbon fibers have anisotropic spreading can be obtained. As described above, anisotropic carbon foam can suppress breakage of the carbon fibers and reduce powder falling off even when a compressive load is applied, and can achieve high restorability.

[0069] The compressive load can be applied by placing a weight such as a graphite plate on the raw resin foam. The compressive load to be applied is preferably 50 Pa or more, more preferably 200 Pa or more. The compressive load to be applied is preferably 2000 Pa or less, more preferably 1500 Pa or less.

[0070] In addition, when compression is performed using a vacuum press or the like, the film thickness after pressing may be determined by a spacer, and the compression ratio may be controlled by dividing the original thickness by the thickness of the spacer, instead of controlling the press load. In this case, the compression ratio is preferably 4 times or more, more preferably 10 times or more, from the viewpoint of providing anisotropy. In addition, the compression ratio is preferably 100 times or less, more preferably 50 times or less, from the viewpoint of maintaining a three-dimensional structure. The vacuum press is not particularly limited as long as it is capable of discharging active gas and is capable of heating and compressing the resin foam, or is capable of compressing the laminate of carbon foam. For example, a heat treatment furnace equipped with a top plate for pressing the resin foam, a heater for heating the top plate, a gas exhaust port for discharging gas from the inside of the apparatus, and a vacuum pump for reducing the pressure inside the apparatus to create a vacuum can be used.

[0071] When a compressive load is applied to the raw resin foam, the diffusion of the decomposable desorbed gas is suppressed by a weight such as a graphite plate, etc. Therefore, in the temperature-raising step, it is particularly preferable to reduce the temperature-raising rate and continue to evacuate the furnace while supplying an inert gas into the furnace, in order to promote the discharge of the decomposable gas, as compared with the case where a compressive load is not applied.

[0072] For example, when the raw material resin foam is a melamine resin foam, the heating rate is preferably 5°C / min or less in a temperature range (first temperature range) of 200°C or more and less than 800°C, and more preferably 2°C / min or less in a temperature range (second temperature range) of 300°C or more and less than 400°C where the rate of increase in the amount of desorbed gas is high. Also, in the temperature range (first temperature range) of 200°C or more and less than 800°C, it is preferable to supply an inert gas such as nitrogen gas or argon gas into the heat treatment furnace.

[0073] The compressive stress may be applied to the raw material resin foam from two directions, not just one direction.

[0074] (Cathode catalyst layer) The cathode catalyst layer is composed of a precious metal supported catalyst and a proton conductive ionomer, and is arranged in the order of the cathode diffusion layer, the cathode catalyst layer, and the solid polymer electrolyte membrane. From the viewpoint of reducing contact resistance, it is preferable that these layers are bonded to each other or that the layers are in direct contact with each other.

[0075] From the viewpoint of catalytic activity, the catalyst layer of the present embodiment preferably contains at least one catalyst metal selected from the group consisting of platinum, ruthenium, rhodium, palladium, iridium, molybdenum, rhenium, tungsten, titanium, nickel, copper, zinc, silver, tin, gold, lead, and lanthanoids.

[0076] The catalyst layer of the present embodiment preferably has a structure in which the catalyst metal is supported on a conductive carrier. The carrier is not particularly limited, but examples thereof include carbon particles, alumina, silica, zeolite, mesoporous materials, etc. By supporting fine particles of the catalyst metal on a carrier, the amount of the catalyst metal used is reduced, and the specific surface area per volume of the catalyst metal tends to be increased, so that the catalytic activity tends to be further improved. The conductive support in the catalyst layer of this embodiment is preferably a carbon material from the viewpoints of physical stability when supporting the catalytic metal, conductivity at the contact point with the catalytic metal, chemical stability against the electrolyte, electrochemical stability in an electrolytic environment, and cost efficiency. Also, from the viewpoint of forming a network structure, which is a more preferred form of this embodiment described below, by a catalyst ink coating method, the conductive support is preferably particulate. From the above viewpoints, it is even more preferable that the conductive support is carbon particles.

[0077] The catalyst layer of this embodiment has a structure in which the catalytic metal and the conductive support are in contact with each other, and this structure is referred to as a network structure. It is preferable that the network structure exhibits electrical conductivity. Since the catalytic metal and the conductive support have a network structure in which they are in contact with each other, the network structure has electrical conductivity, and thus tends to be able to supply electrons from an external circuit to catalytic active sites more efficiently.

[0078] The method for obtaining the network structure is not particularly limited, but may be, for example, a catalyst ink coating method described below.

[0079] Furthermore, the method for confirming the conductivity due to the network structure is not particularly limited, but examples thereof include a simple method of contacting an electrode of a tester with the catalyst layer to measure the resistance value, and more strictly, a method of measuring the sheet resistance value or volume resistivity using a sheet resistance measuring device or the like.

[0080] The method for forming the catalyst layer of the present embodiment is not particularly limited, and examples thereof include a catalyst ink coating method described below. In the catalyst ink coating method, a catalyst ink is first prepared that contains the organic polymer and the catalytic metal and / or the conductive carrier, and in which the organic polymer, the catalytic metal and / or the conductive carrier are uniformly dispersed in water and / or an organic solvent. When preparing the catalyst ink, a dispersant may be used to uniformly disperse the organic polymer, the catalytic metal and / or the conductive carrier. In addition, a method for uniformly dispersing the organic polymer, the catalytic metal and / or the conductive carrier after mixing them in water and / or an organic solvent is not particularly limited, and examples thereof include a method of dispersing with an ultrasonic cleaner, a method of dispersing with a magnetic stirrer, and a method of dispersing with a homogenizer. The catalyst ink prepared as described above is applied to a substrate to form a wet film. A method for applying the catalyst ink is not particularly limited, and examples thereof include a screen printing method using a squeegee and a coating method using an applicator. The water and / or organic solvent contained in the wet film is dried at room temperature, and then the wet film is heated to bond the organic polymer to the catalytic metal and / or the conductive support. The heating temperature is preferably equal to or higher than the glass transition point of the ionomer, and more preferably equal to or lower than the decomposition temperature of the ionomer.

[0081] In addition, when heating, it is preferable to apply an appropriate load in the vertical direction to the wet film, since the organic polymer and the catalytic metal and / or the conductive support are more firmly bonded to each other, and the film after heating tends to be stable. The wet film is heated for a sufficient time (e.g., 30 minutes) as described above, and then cooled to room temperature to obtain the catalyst layer of this embodiment.

[0082] (Solid polymer electrolyte membrane) The solid polymer electrolyte membrane of this embodiment is formed from a material having proton conductivity, and while it allows protons to pass through it, it separates the cathode chamber and the anode chamber and suppresses the mixing and diffusion of substances.

[0083] The thickness of the electrolyte membrane is preferably 10 μm or more, more preferably 20 μm or more, and most preferably 25 μm or more from the viewpoint of suppressing diffusion of substances, while being preferably 300 μm or less, more preferably 250 μm or less, and most preferably 200 μm or less from the viewpoint of reducing resistance.

[0084] The electrolyte membrane of the present embodiment contains a perfluorocarbon polymer having an ion exchange group. The perfluorocarbon polymer has an equivalent mass EW of the ion exchange group of 600 g / eq or more and 2000 g / eq or less.

[0085] The electrolyte membrane of this embodiment has a dimensional change rate in at least one of the X direction and the Y direction when immersed in the following 2M aqueous sulfuric acid solution of 80% or more and less than 100%. (Dimensional change rate due to immersion in 2M sulfuric acid solution) A test electrolyte membrane having a water content of 1% or less is prepared, and the test electrolyte membrane is immersed in a 2M aqueous sulfuric acid solution at 25°C for 30 minutes. The dimensional change rate in the X direction and the Y direction perpendicular to the X direction on the surface of the test electrolyte membrane is calculated by the following formula. Dimensional change rate (%) = (dimension in a specific direction after immersion) / (dimension in a specific direction before immersion) x 100

[0086] The electrolyte membrane of this embodiment has a dimensional change rate of 80% or more and less than 100% in at least one of the X direction and the Y direction, and a dimensional change rate of 115% or more in the Z direction, when immersed in distilled water as described below. (Dimensional change rate due to immersion in distilled water) A test electrolyte membrane having a water content of 1% or less is prepared, and the test electrolyte membrane is immersed in distilled water at 25°C for 30 minutes. The dimensional change rates of the test electrolyte membrane in the X direction, the Y direction perpendicular to the X direction, and the Z direction perpendicular to the X direction and the Y direction are calculated. Dimensional change rate (%) = (dimension in a specific direction after immersion) / (dimension in a specific direction before immersion) x 100

[0087] By using a configuration that satisfies the above-mentioned dimensional change rate due to immersion in a 2M aqueous sulfuric acid solution and the dimensional change rate due to immersion in distilled water, the cluster structure (pathway for ions and water molecules) in the electrolyte membrane is made complex, and further, swelling is suppressed due to high crystallinity, so that an electrolysis cell for producing organic hydrides can be provided in which water diffusion from the anode chamber to the cathode chamber is suppressed.

[0088] (Perfluorocarbon polymer) The electrolyte membrane of this embodiment contains a perfluorocarbon polymer having an ion exchange group. The ion exchange group is not particularly limited, but examples thereof include -COOH group, -SO 3 H group, -PO 3 H 2 Examples of the salt include, but are not limited to, alkali metal salts, alkaline earth metal salts, and amine salts.

[0089] (equivalent mass EW) From the viewpoints of improving proton conductivity and reducing cell resistance, the perfluorocarbon polymer is preferably 2000 g / eq or less, more preferably 1700 g / eq or less, and most preferably 1500 g / eq or less, while from the viewpoints of suppressing water migration from the anode chamber to the cathode chamber, the perfluorocarbon polymer is preferably 600 g / eq or more, more preferably 700 g / eq or more, and most preferably 750 g / eq or more. The equivalent weight EW means the dry weight (g) of the perfluorocarbon polymer per equivalent of the ion exchange group. The equivalent mass EW of a perfluorocarbon polymer can be measured by salt-substituting the perfluorocarbon polymer and back-titrating the resulting solution with an alkali solution. The equivalent weight EW can be adjusted by the copolymerization ratio of the fluorine-based monomers that are the raw materials of the perfluorocarbon polymer, the selection of the monomer species, and the like.

[0090] The perfluorocarbon polymer preferably contains a structure represented by the following formula (1). -[CF 2 -CX1X2]a-[CF 2 -CF(-O-(CF 2 -CF(CF 2 X3))b-Oc-(CFR1)d-(CFR2)e-(CF 2 )f-X4)]g- (1) In the formula (1), X1, X2, X3, R1, R2 and a to g are defined as follows. X1, X2 and X3 each independently represent a halogen atom or a perfluoroalkyl group having 1 to 3 carbon atoms. The halogen atom is not particularly limited, but examples thereof include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The perfluoroalkyl group having 1 to 3 carbon atoms is not particularly limited, but examples thereof include a trifluoromethyl group, a pentafluoroethyl group, a perfluoro n-propyl group, and a perfluoroisopropyl group. From the viewpoint of chemical stability such as resistance to oxidative deterioration of the polymer, X1, X2 and X3 are preferably each independently a fluorine atom or a perfluoroalkyl group having 1 to 3 carbon atoms, and more preferably a fluorine atom. X4 is a -COOZ group, -SO 3 Z group, -PO 3 Z 2 Group or -PO 3 It is an HZ group. Z is a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, or NH4 , NH 3 R11, NH 2 R11R12, NHR11R12R13, NR11R12R13R14. Here, R11, R12, R13, and R14 are each independently an alkyl group or an aryl group. The alkyl groups of R11, R12, R13, and R14 are preferably alkyl groups having 1 to 6 carbon atoms, more preferably a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, or an n-hexyl group. The aryl group is not particularly limited, and examples thereof include a phenyl group and a naphthyl group. In addition, when X4 is a -PO 3 Z 2 group, Z may be the same or different. The alkali metal atom is not particularly limited, and examples thereof include a lithium atom, a sodium atom, and a potassium atom. The alkaline earth metal atom is not particularly limited, and examples thereof include a calcium atom and a magnesium atom. From the viewpoint of chemical stability such as the oxidation degradation resistance of the polymer, X4 is preferably SO 3 Z. R1 and R2 are each independently a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms, or a fluorochloroalkyl group. Here, the halogen atoms of R1 and R2 are not particularly limited, and examples thereof include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Among these, a fluorine atom is preferred. a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d, e, and f are each independently an integer from 0 to 6. However, d, e, and f are not simultaneously 0. In addition, the structural unit of [CF 2 -CX1X2] and the structural unit of [CF 2 -CF(-O-(CF 2 -CF(CF 2 X3))b - Oc - (CFR1)d - (CFR2)e - (CF2)f - X4)] are not particularly limited in their sequence order and may be random or block.

[0091] The perfluorocarbon polymer in this embodiment is preferably a perfluorocarbon sulfonic acid resin (hereinafter, also referred to as "PFSA resin"), since the effects of this embodiment tend to be more pronounced. The PFSA resin in this embodiment is a resin in which perfluorocarbon is bonded as a side chain to a main chain consisting of a PTFE skeletal chain, and one or two or more sulfonic acid groups (some of which may be in the form of a salt in some cases) are bonded to each side chain. PFSA resin is -[CF 2 CF 2 It is preferable that the repeating unit contains a repeating unit represented by the formula (3), (4-1) or (4-2) below. CF 2 =CF(-O-(CF 2 CFXO)n-[A]) (3) In formula (3), X is F or a perfluoroalkyl group having 1 to 3 carbon atoms, and n is an integer of 0 to 5. [A] is (CF 2 )m-SO 3 H, and m is an integer from 0 to 6. However, n and m cannot be 0 at the same time. CF 2 =CF-O-(CF 2 )P-CFX(-O-(CF 2 )K-SO 3 H) (4-1) CF 2 =CF-O-(CF 2 )P-CFX(-(CF 2 )LO-(CF 2 )m-SO 3 H) (4-2) (In formulas (4-1) and (4-2), X is a perfluoroalkyl group having 1 to 3 carbon atoms, P is an integer from 0 to 12, K is an integer from 1 to 5, L is an integer from 1 to 5, and m is an integer from 0 to 6. However, K and L may be the same or different, and P, K, and L are not 0 at the same time.)

[0092] In addition, PFSA resin is -[CF 2 CF2 ]- and -[CF 2 -CF(-O-(CF 2 CFXO)n-(CF 2 )m-SO 3 H)]-(wherein X is F or CF 3 where n is an integer of 0 to 5, and m is an integer of 0 to 12. However, n and m cannot be 0 at the same time. 2 -CF(-O-(CF 2 CFXO)n-(CF 2 )m-SO 3 H)]-(wherein X is CF 3 where n is 0 or 1, and m is an integer from 0 to 12. However, n and m are not 0 at the same time.) is more preferable. When the PFSA resin is a copolymer having the above structure and has a predetermined equivalent mass EW, the obtained electrolyte membrane tends to have sufficient hydrophilicity and to have strong resistance to electrolyte active materials, such as pentavalent vanadium.

[0093] Furthermore, the -[CF 2 -CF(-O-(CF 2 CFXO)n-(CF 2 )m-SO 3 H)]- (wherein n is 0 and m is an integer of 1 to 6), or a repeating unit represented by formula (4-1) or a repeating unit represented by formula (4-2) -[CF 2 -CF(-O-(CF 2 )P-CFX(-O-(CF 2 )K-SO 3 H))]- and -[CF 2 -CFX(-O-(CF 2 )P-CFX(-(CF 2 )LO-(CF 2 )m-SO 3 When the repeating units include both the cyclic and cyclic repeating units, the equivalent weight (EW) tends to be low and the hydrophilicity of the resulting electrolyte membrane tends to be high.

[0094] The perfluorocarbon polymer represented by formula (1) in this embodiment preferably has a structure represented by the following formula (2) because the effects of this embodiment tend to be more remarkable. -[CF 2 CF 2 a-[CF 2 -CF(-O-(CF 2 )m-SO 3 H)]g- (2) In formula (2), a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1, and m is an integer from 1 to 6.

[0095] The perfluorocarbon polymer in this embodiment is not particularly limited as long as it has a structure represented by formula (1) or formula (2), and it may contain other structures.

[0096] The perfluorocarbon polymer in this embodiment may be one in which intermolecular partial crosslinking reaction is carried out directly or indirectly with an ion exchange group from the viewpoint of controlling solubility or swelling property. By performing partial crosslinking, for example, even if the equivalent weight EW of the perfluorocarbon polymer is about 500 g / eq, the water solubility of the perfluorocarbon polymer can be reduced (water resistance is improved).

[0097] Also, even when the perfluorocarbon polymer has a low melt flow value (has a high molecular weight), the above-mentioned partial crosslinking can increase the entanglement between molecules and reduce solubility and excessive swelling property.

[0098] Examples of the partial crosslinking reaction include a reaction between an ion exchange group and a functional group of another molecule or the main chain, or a reaction between ion exchange groups, and a crosslinking reaction (covalent bond) via an antioxidant low molecular compound, oligomer or polymer substance, etc. In some cases, it may be a reaction with a salt-forming substance (including an ionic bond with -SO3H group). Examples of the antioxidant low molecular compound, oligomer or polymer substance include polyhydric alcohols and organic diamines.

[0099] The molecular weight of the perfluorocarbon polymer in this embodiment is not particularly limited, but the melt flow index (MFI) value measured in accordance with ASTM:D1238 (measurement conditions: temperature 270°C, load 2160 g) is preferably 0.05 g / 10 min or more and 50 g / 10 min or less, more preferably 0.1 g / 10 min or more and 30 g / 10 min or less, and even more preferably 0.5 g / 10 min or more and 20 g / 10 min or less. (Method of producing perfluorocarbon polymer)

[0100] The perfluorocarbon polymer in the present embodiment is not particularly limited, but can be obtained, for example, by producing a precursor of a perfluorocarbon polymer having an ion exchange group (hereinafter also referred to as a "resin precursor") and then subjecting it to a hydrolysis treatment.

[0101] In the case of the PFSA resin, for example, it can be obtained by hydrolyzing a PFSA resin precursor consisting of a copolymer of a fluorinated vinyl ether compound represented by the following formula (6) or formula (7) and a fluorinated olefin monomer represented by the following formula (8). CF 2 =CF-O-(CF 2 CFXO)nA (6) (In formula (6), X is F or a perfluoroalkyl group having 1 to 3 carbon atoms, n is an integer of 0 to 5, A is (CF2)mW, where m is an integer of 0 to 6, n and m are not simultaneously 0, and W is a functional group that can be converted to a -SO3H group by hydrolysis.) CF 2 =CF-O-(CF 2 )P-CFX(-O-(CF 2 )KW) or CF 2 =CF-O-(CF 2 )P-CFX(-(CF 2 )LO-(CF 2 )mW) (7) (In formula (7), X is a perfluoroalkyl group having 1 to 3 carbon atoms, P is an integer from 0 to 12, K is an integer from 1 to 5, and L is an integer from 1 to 5, where L, K, and m are not all 0 at the same time, m is an integer from 0 to 6, and W is a functional group that can be converted to a -SO3H group by hydrolysis.) CF 2 =CFZ (8) (In the formula (8), Z is H, Cl, F, a perfluoroalkyl group having 1 to 3 carbon atoms, or a cyclic perfluoroalkyl group which may contain oxygen as a ring-constituting atom.) W in the formula (6) and the formula (7) is not particularly limited, but may be, for example, -SO 2 F group, -SO 2 Cl group, -SO 2 In the above formula (6) and formula (7), X is a CF 3 and W is -SO 2 In the above formula (8), Z is preferably F. Among them, n=0, m=an integer of 1 to 6, and X is CF 3 and W is -SO 2 It is more preferable that the F group, Z, is F, since this tends to result in a solution with high hydrophilicity and a high resin concentration.

[0102] The resin precursor in this embodiment can be synthesized by a known method, for example, by polymerizing a vinyl fluoride compound having a group (an ion exchange group precursor group) that can be converted to an ion exchange group (X4 in formula (1)) by hydrolysis or the like, and a fluorinated olefin such as tetrafluoroethylene (hereinafter also referred to as "TFE") in the presence of a radical generator such as a peroxide. The polymerization method is not particularly limited, and examples of the polymerization method that can be used include a method of polymerizing the vinyl fluoride compound and the like and a fluorinated olefin gas by filling and dissolving them in a polymerization solvent such as a fluorinated hydrocarbon and reacting them together (solution polymerization), a method of polymerizing the vinyl fluoride compound itself as a polymerization solvent without using a solvent such as a fluorinated hydrocarbon (bulk polymerization), a method of polymerizing the vinyl fluoride compound and a fluorinated olefin gas by filling an aqueous solution of a surfactant as a medium and reacting them together (emulsion polymerization), a method of polymerizing the vinyl fluoride compound and a fluorinated olefin gas by filling an aqueous solution of a surfactant and an emulsifier such as alcohol, emulsifying the mixture, and reacting them together (emulsion polymerization), and a method of polymerizing the vinyl fluoride compound and a fluorinated olefin gas by filling an aqueous solution of a suspension stabilizer, suspending the mixture, and reacting them together (suspension polymerization).

[0103] The resin precursor in this embodiment may be prepared by any of the polymerization methods described above. In addition, a block-shaped or tapered polymer obtained by adjusting the polymerization conditions such as the supply amount of TFE gas may be used as the resin precursor.

[0104] The resin precursor may be one in which impurity terminals generated in the resin molecular structure during the polymerization reaction or portions that are easily oxidized due to their structure (CO groups, H-bond portions, etc.) are fluorinated by treating such portions under fluorine gas using a known method.

[0105] The resin precursor may contain ion exchange group precursor groups (e.g., -SO 2 A part of the F groups may be partially (including intermolecularly) imidized (such as alkylimidized).

[0106] The molecular weight of the resin precursor is not particularly limited, but the melt flow index (MFI) value of the precursor measured in accordance with ASTM:D1238 (measurement conditions: temperature 270°C, load 2160 g) is preferably 0.05 g / 10 min or more and 50 g / 10 min or less, more preferably 0.1 g / 10 min or more and 30 g / 10 min or less, and even more preferably 0.5 g / 10 min or more and 20 g / 10 min or less.

[0107] The shape of the resin precursor is not particularly limited, but from the viewpoint of increasing the treatment speed in the hydrolysis treatment and acid treatment described later, it is preferable to use a shape of, for example, 0.5 cm 3 The resin precursor is preferably in the form of pellets, dispersion liquid, or powder particles as described below. Among them, it is more preferable to use a powder form after polymerization. From the viewpoint of cost, a resin precursor in the form of a film obtained by extrusion molding may be used.

[0108] The method for producing the perfluorocarbon polymer in this embodiment from the resin precursor is not particularly limited, but for example, the resin precursor may be extruded through a nozzle or die using an extruder and then subjected to a hydrolysis treatment, or the product obtained upon polymerization may be used as is, i.e., in the form of a dispersion, or precipitated and filtered into a powder form, and then subjected to a hydrolysis treatment.

[0109] Specifically, the resin precursor obtained as described above and molded as necessary can be subsequently immersed in a basic reaction liquid and subjected to hydrolysis treatment. The basic reaction liquid used for hydrolysis treatment is not particularly limited, but examples thereof include an aqueous solution of an amine compound such as dimethylamine, diethylamine, monomethylamine, and monoethylamine, and an aqueous solution of an alkali metal or alkaline earth metal hydroxide. Among these, an aqueous solution of sodium hydroxide or potassium hydroxide is preferred. When an alkali metal or alkaline earth metal hydroxide is used, its content is not particularly limited, but it is preferably 10% by mass or more and 30% by mass or less with respect to the entire reaction liquid. It is more preferred that the reaction liquid further contains a swelling organic compound such as methyl alcohol, ethyl alcohol, acetone, and dimethyl sulfoxide (DMSO). The content of the swelling organic compound is preferably 1% by mass or more and 30% by mass or less with respect to the entire reaction liquid.

[0110] After the resin precursor is hydrolyzed in a basic reaction liquid, it is thoroughly washed with warm water or the like, and then acid treatment is performed. The acid used in the acid treatment is not particularly limited, but examples thereof include mineral acids such as hydrochloric acid, sulfuric acid, and nitric acid, and organic acids such as oxalic acid, acetic acid, formic acid, and trifluoroacetic acid. A mixture of these acids and water is preferable. The above acids may be used alone or in combination of two or more kinds. The basic reaction liquid used in the hydrolysis treatment may be removed in advance before the acid treatment by treating with a cation exchange resin, for example.

[0111] The ion exchange group precursor group of the resin precursor is protonated by the acid treatment to generate an ion exchange group. For example, in the case of a resin precursor produced using the formula (6), W in the formula (6) is protonated by the acid treatment to generate -SO 3 The perfluorocarbon polymer obtained by hydrolysis and acid treatment can be dispersed or dissolved in a protic organic solvent, water, or a mixed solvent of the two, and can be made into a suspension or solution.

[0112] The perfluorocarbon polymer may contain an alkali metal, an alkaline earth metal, or other radically decomposable transition metal (such as a Ce compound or a Mn compound) in the form of a partial salt with these metals (about 0.01 to 5 equivalent % of the total ion exchange group equivalent), either alone or in combination with a basic polymer described below.

[0113] From the viewpoint of improving electrical resistance and mechanical strength, the electrolyte membrane of the present embodiment preferably contains a mixture of two or more types of perfluorocarbon polymers having ion exchange groups and different monomer structures.

[0114] By mixing two or more types of perfluorocarbon polymers, it is possible to exhibit excellent properties by combining the functions of each.

[0115] In order to improve the mechanical strength, when two or more kinds of perfluorocarbon polymers are mixed, the ratio of the polymer having a higher equivalent weight EW is preferably greater than 50% by mass, more preferably greater than 55% by mass, and even more preferably greater than 60% by mass. Since the polymer having a higher equivalent weight EW tends to have higher crystallinity, the above ratio tends to exhibit higher mechanical strength.

[0116] (Method for producing raw membrane of perfluorocarbon polymer) The raw material membrane used in the production of the electrolyte membrane of this embodiment can be obtained by processing a precursor resin or a perfluorocarbon polymer into a film by a known method. For example, a method can be used in which the precursor of the perfluorocarbon polymer described above is melt-kneaded, formed into a film using an extruder, and then hydrolyzed to form ion exchange groups. Alternatively, the perfluorocarbon polymer may be dispersed in a solvent once, and then cast onto a substrate to form a film.

[0117] (Method of stretching perfluorocarbon polymer raw material film) The method for producing an electrolyte membrane according to this embodiment includes a step of stretching a raw material membrane under heating. The manufacturing method of this embodiment further includes a relaxation treatment step in a cooling process after the stretching step. That is, the electrolyte membrane of the present embodiment is stretched under heating and then cooled preferably at a relaxation rate of 0.1% to 5.0%, thereby preventing crazes and suppressing self-discharge.

[0118] The stretching treatment in this embodiment can be carried out by, for example, uniaxial stretching, simultaneous biaxial stretching, or sequential biaxial stretching.

[0119] In the present invention, the X-axis direction refers to the winding direction (MD direction) when a long membrane is produced by extrusion film production, cast film production, or the like, and the Y-axis direction refers to the direction perpendicular to the MD direction (TD direction).

[0120] The stretching ratio is preferably 1.5 times, more preferably 1.8 times, even more preferably 2.1 times, and even more preferably 2.5 times in at least one axial direction from the viewpoint of suppressing the bending of the membrane when incorporated into a cell. Also, from the viewpoint of suppressing the occurrence of crazes and improving the selectivity of the permeating ions, it is preferably 8 times or less, more preferably 6 times or less, even more preferably 5 times or less, and even more preferably 4 times or less. The stretching ratio in the present invention can be set independently in the X-axis direction and the Y-axis direction. The areal stretching ratio obtained by multiplying the stretching ratio in the X-axis direction and the stretching ratio in the Y-axis direction is preferably 2.2 times or more, more preferably 3.2 times or more, and even more preferably 4.0 times or more from the viewpoint of improving the selectivity of the permeating ions. The areal stretching ratio is preferably 50 times or less, more preferably 40 times or less, and even more preferably 30 times or less from the viewpoint of suppressing the occurrence of crazes.

[0121] From the viewpoint of controlling the cluster size in the electrolyte membrane and further improving the selective permeability of ions, it is preferable to perform biaxial stretching. That is, the electrolyte membrane of the present embodiment is preferably a biaxially stretched electrolyte membrane. In the present embodiment, a membrane of a perfluorocarbon polymer having an ion exchange group is first subjected to simultaneous biaxial stretching in a temperature range from 20°C lower to 40°C higher than the α-dispersion temperature of the polymer.

[0122] The α-dispersion temperature of a perfluorocarbon polymer membrane having an ion exchange group is the temperature at which the main chain of the polymer is thought to start thermal motion, as measured by a dynamic viscoelasticity measuring device. For example, the α-dispersion temperature of a polymer such as nylon is generally much higher than room temperature, so that the thermal motion of the main chain can be greatly reduced by cooling the polymer to below the α-dispersion temperature after the end of stretching, thereby effectively stabilizing the stretching orientation.

[0123] For example, when the ion exchange group is a sulfonic acid group, the α-dispersion temperature of the perfluorocarbon polymer is in the vicinity of 110 to 140° C. Therefore, if the α-dispersion temperature is assumed to be 140° C., the stretching temperature in the stretching step is set in the temperature range of 120° C. or more and 180° C. or less.

[0124] This embodiment is also characterized in that the membrane stretched in the stretching step is subsequently heat-treated at a temperature higher than the stretching temperature while being fixed.

[0125] Fixing the membrane refers to fixing the periphery of the membrane so as to prevent the orientation of the stretched membrane from relaxing. Specifically, it is sufficient that the edges of the membrane are fixed, and the edges of the electrolyte membrane can be fixed using a device such as a chuck-type tenter.

[0126] The stretching speed during the stretching process is preferably 10 mm / min or more, more preferably 50 mm / min or more, and even more preferably 90 mm / min or more from the viewpoint of suppressing orientation relaxation, while the stretching speed is preferably 500 mm / min or less, more preferably 300 m / min or less, and even more preferably 200 m / min or less from the viewpoint of suppressing breakage.

[0127] The method for producing the electrolyte membrane of the present embodiment preferably further includes a step of performing a relaxation treatment in the cooling process after the stretching treatment.

[0128] In this embodiment, the relaxation treatment after the stretching treatment is performed by narrowing the chuck gap by a predetermined distance. The ratio of the narrowed distance to the chuck gap (relaxation rate) is preferably 0.1% or more, more preferably 0.2% or more, and even more preferably 0.4% or more, from the viewpoint of suppressing breakage. On the other hand, from the viewpoint of suppressing orientation relaxation, it is preferably 3% or less, more preferably 2% or less, and even more preferably 1.5% or less. This allows the stress due to shrinkage during cooling to be relaxed, and a stretched membrane can be obtained without generating minute defects in the membrane, and an electrolyte membrane that suppresses water permeation from the anode chamber to the cathode chamber can be obtained when an electrolytic cell for producing organic hydrides is formed.

[0129] (flatness) The flatness index of the electrolyte membrane of this embodiment is preferably less than 1.2, more preferably less than 1.1, and even more preferably less than 1.05, from the viewpoint of good workability during assembly of an electrolytic cell for producing organic hydrides. The flatness index of the electrolyte membrane is the ratio of the length along the membrane surface to the projected dimension of the membrane. A specific measurement method is as described in the Examples. The flatness index of the electrolyte membrane may be any surface that satisfies the above numerical value, and may be any surface cut out to 140 mm square.

[0130] (craze area ratio) In the electrolyte membrane of this embodiment, the craze area ratio is preferably 1.5% or less, more preferably 1.0% or less, and most preferably 0.8% or less, from the viewpoint of suppressing water permeation from the anode chamber to the cathode chamber. The craze area ratio is, for example, 0% or more. The craze area means the ratio of the area of ​​the region with a transmittance of 10% or more to the total area of ​​the electrolyte membrane. The craze area can be obtained by measuring the visible light transmittance distribution in the electrolyte membrane surface, and more specifically, can be measured by the method shown in the Examples.

[0131] (orientation parameter) The orientation parameter of this embodiment is preferably 0.05 or more, more preferably 0.15 or more, and even more preferably 0.20 or more, either in the membrane plane or in the plane perpendicular to the membrane plane (outside the membrane plane), from the viewpoint of permeation ion selectivity. The upper limit of the orientation parameter is not particularly limited, but from the viewpoint of suppressing a decrease in membrane strength due to the occurrence of crazes, it is preferably 0.70 or less, more preferably 0.60 or less, and even more preferably 0.50 or less.

[0132] The orientation parameter of the plane perpendicular to the film surface (hereinafter also referred to as "out-of-plane orientation parameter") is preferably 0.15 or more, more preferably 0.20 or more, and even more preferably 0.25 or more, from the viewpoint of suppressing self-discharge. The upper limit of the orientation parameter of the plane perpendicular to the film surface is not particularly limited, but is preferably 0.70 or less, more preferably 0.60 or less, and even more preferably 0.50 or less.

[0133] By orienting the electrolyte membrane under specific conditions so that the orientation parameters fall within the range described above, the cluster shape in the membrane thickness direction can be controlled, and a membrane can be formed in which crazes, which are microscopic defects within the membrane, are suppressed. This makes it possible to effectively suppress the permeation of water from the anode chamber to the cathode chamber without suppressing the movement of protons. The orientation parameter q in and out of the film plane can be calculated by approximating the azimuthal intensity distribution I(φ) of the peak derived from ion clusters in small-angle X-ray scattering (described later) using the orientation function shown in the following formula:

number

[0134] (Ion cluster diameter) The ion cluster diameter in this embodiment can be measured by small angle X-ray scattering (SAXS) in the membrane surface direction and in the direction perpendicular to the membrane surface. The ion cluster diameter in the membrane surface direction is preferably 2.5 nm or more, more preferably 2.7 nm or more, and even more preferably 2.8 nm or more, from the viewpoint of reducing the resistance component when an electrolytic cell for producing organic hydrides is formed. Moreover, the ion cluster diameter in the membrane surface direction is preferably 3.9 nm or less, more preferably 3.5 nm or less, and even more preferably 3.2 nm or less, from the viewpoint of suppressing swelling of the electrolyte membrane and suppressing water permeation from the anode chamber to the cathode chamber.

[0135] The ion cluster diameter in the direction perpendicular to the membrane surface (hereinafter, "ion cluster diameter in the out-of-membrane direction") is preferably 3.0 nm or more, more preferably 3.3 nm or more, and even more preferably 3.4 nm or more, from the viewpoint of suppressing water permeation from the anode chamber to the cathode chamber. The ion cluster diameter in the out-of-membrane direction is not particularly limited, but is preferably 3.9 nm or less, more preferably 3.7 nm or less, and even more preferably 3.6 nm or less.

[0136] (crystal long period) The crystal long period measured by small-angle X-ray scattering in the electrolyte membrane of this embodiment is a scattering vector of small-angle X-ray scattering of 0.1 to 1.0 nm. -1 The Bragg equation is used to determine the position of the peak that arises in the range due to the periodicity of the electron density difference between the crystal and amorphous regions.

[0137] The crystal long period measured by small angle X-ray scattering is preferably 5 nm or more and 60 nm or less, more preferably 10 nm or more and 55 nm or less, even more preferably 20 nm or more and 50 nm or less, and even more preferably 30 nm or more and 50 nm or less.

[0138] The peak intensity of the long crystal period measured by small-angle X-ray scattering is the scattering vector of small-angle X-ray scattering 0.1 to 1.0 nm. -1 It is defined as the ratio of the difference between the peak top intensity and the baseline intensity to the baseline intensity of the crystal long period peak occurring in the range. From the viewpoint of improving the current efficiency, the peak intensity is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and even more preferably 0.1 or less.

[0139] In the present embodiment, the thickness of the raw material membrane to be stretched can be calculated according to the target stretch ratio.

[0140] The electrolyte membrane of this embodiment is suitable for use as a diaphragm in an electrolysis cell for producing organic hydrides. In general, an electrolyte membrane made of a perfluorocarbon polymer having an ion exchange group swells and undergoes dimensional changes when it comes into contact with distilled water, an aqueous sulfuric acid solution, or an aqueous solution. The electrolyte membrane of this embodiment is inhibited from swelling even when it comes into contact with these aqueous solutions, and dimensional changes in the membrane surface direction are inhibited. Therefore, even if the electrolyte membrane is filled with an aqueous anode solution and a substance to be hydrided when assembling an electrolysis cell for producing organic hydrides, the membrane does not sag, and the membrane can be used without deteriorating its electrical properties.

[0141] (Dimensional change rate due to immersion in 2M sulfuric acid solution) In the dimensional change rate of the electrolyte membrane of this embodiment when immersed in a 2M aqueous sulfuric acid solution, the dimensional change rate in at least one of the X direction and the Y direction is 80% or more and less than 100% from the viewpoint of not causing distortion in the electrolysis cell for producing organic hydride and not deteriorating the electrical characteristics. A test electrolyte membrane having a water content of 1% or less is prepared, and the test electrolyte membrane is immersed in a 2M aqueous sulfuric acid solution at 25°C for 30 minutes. The dimensional change rate in the X direction and the Y direction perpendicular to the X direction on the surface of the test electrolyte membrane is calculated by the following formula. Dimensional change rate (%) = (dimension in a specific direction after immersion) / (dimension in a specific direction before immersion) x 100

[0142] In the dimensional change rate of the electrolyte membrane of this embodiment in a 2M sulfuric acid aqueous solution, the dimensional change rate in at least one of the X direction and the Y direction is preferably 99.8% or less, more preferably 99.5% or less, even more preferably 99.2% or less, and even more preferably 99.0% or less, from the viewpoint of not causing distortion in the electrolytic cell for producing organic hydrides and not deteriorating electrical characteristics. The dimensional change rate in at least one of the X direction and the Y direction is preferably 85% or more, more preferably 90% or more, even more preferably 95.0% or more, and even more preferably 97.0% or more, from the viewpoint of reducing stress and improving long-term durability.

[0143] More specifically, the dimensional change rate due to immersion in a 2M sulfuric acid aqueous solution can be evaluated by, for example, cutting an electrolyte membrane with a moisture content adjusted to 1% or less into a square piece with a length of 7 cm, immersing it in a 2M sulfuric acid aqueous solution at 25°C for 30 minutes, and then measuring the dimensions. The moisture content can be measured by the method described in the Examples. If the moisture content exceeds 1%, it can be adjusted by drying it for 2 hours in an oven heated to 50°C under reduced pressure and measuring the moisture content again. It should be noted that the X direction is a direction that is arbitrarily selected on the film surface, and the Y direction means a direction perpendicular to the X direction on the film surface. The dimensional change rate due to immersion in a 2M sulfuric acid solution can be evaluated with high accuracy, for example, by using a D2XY-KSH reading microscope manufactured by Nippon Kogyo Seisakusho. If it is difficult to obtain a square test piece measuring 7 cm on one side, it can also be measured by using a rectangular test piece measuring 1 cm x 3 cm. In this case, it can be evaluated with higher accuracy by using two test pieces so that the arbitrary X and Y directions on the film surface are each 3 cm.

[0144] The dimensional change rate due to immersion in a 2M aqueous sulfuric acid solution can be adjusted to the above-mentioned range by adjusting, for example, the type of perfluorocarbon polymer used in the electrolyte membrane, the stretch ratio and relaxation rate during production of the electrolyte membrane.

[0145] (Dimensional change rate due to immersion in distilled water) In the dimensional change rate of the electrolyte membrane of this embodiment due to immersion in distilled water, the dimensional change rate in at least one of the X direction and the Y direction is 80% or more and less than 100%, from the viewpoint of not causing distortion in the electrolytic cell for producing organic hydride and not deteriorating the electrical characteristics, and the dimensional change rate in the Z direction is 115% or more. In terms of the dimensional change rate due to immersion in distilled water, the dimensional change rate in at least one of the X direction and the Y direction is preferably 99.8% or less, more preferably 99.5% or less, even more preferably 99.2% or less, and even more preferably 99.0% or less, from the viewpoint of not causing deflection in the electrolytic cell for producing organic hydrides and not deteriorating electrical characteristics. In terms of reducing stress and improving long-term durability, the dimensional change rate in at least one of the X direction and the Y direction is preferably 85% or more, more preferably 90% or more, even more preferably 93.0% or more, and even more preferably 94.0% or more.

[0146] In terms of the dimensional change rate due to immersion in distilled water, the dimensional change rate in the Z direction is preferably 115% or more, more preferably 120% or more, and even more preferably 125% or more, from the viewpoint of retaining water and improving proton conductivity. The dimensional change rate in the Z direction is preferably 160% or less, more preferably 150% or less, even more preferably 140% or less, and even more preferably 130% or less, from the viewpoint of reducing the water content of the membrane and suppressing water permeation from the anode chamber to the cathode chamber.

[0147] More specifically, the dimensional change rate due to immersion in distilled water can be evaluated by cutting an electrolyte membrane with a moisture content adjusted to 1% or less into a 7 cm square piece, immersing it in distilled water at 25°C for 30 minutes, and measuring the dimensions after immersion. The moisture content can be measured by the method described in the Examples. If the moisture content exceeds 1%, it can be adjusted by drying it in an oven heated to 50°C under reduced pressure for 2 hours and measuring the moisture content again. The X direction is an arbitrarily selected direction on the film surface, the Y direction is a direction perpendicular to the X direction on the film surface, and the Z direction is a direction perpendicular to the X and Y directions. The dimensional change rate due to immersion in distilled water can be evaluated with high accuracy, for example, by using a D2XY-KSH reading microscope manufactured by Nippon Kogyo Seisakusho. If it is difficult to obtain a square test piece measuring 7 cm on one side, it can also be measured by using a rectangular test piece measuring 1 cm x 3 cm. In this case, it can be evaluated with higher accuracy by using two test pieces so that the arbitrary X and Y directions on the film surface are each 3 cm. If the electrolyte membrane is swollen with distilled water, it can be dried so that the moisture content of the electrolyte membrane is 1% or less before use in the measurement. If the electrolyte membrane is swollen with something other than distilled water, such as a sulfuric acid solution, it can be washed with distilled water until the washing solution has a pH of 6.0 or more, and then dried so that the moisture content of the electrolyte membrane is 1% or less before use in the measurement.

[0148] The dimensional change rate due to immersion in distilled water can be adjusted to the above-mentioned range by adjusting, for example, the type of perfluorocarbon polymer used in the electrolyte membrane, the stretch ratio and relaxation rate during production of the electrolyte membrane, etc.

[0149] (YI value) The YI value (yellowness index) of the electrolyte membrane of this embodiment is preferably 9.00 or less, more preferably 3.00 or less, and even more preferably 1.00 or less, from the viewpoint of suppressing resistance caused by elution of components in the membrane and adhesion to the catalyst layer. The increase in the YI value of the electrolyte membrane occurs due to the decomposition or denaturation of the solvent, additives, and low molecular weight components present in the electrolyte membrane caused by heating. The YI value of the electrolyte membrane can be kept low by removing these components in advance by washing with distilled water or the like, or by drying under reduced pressure at 50°C or less, or by drying under an inert gas flow. In addition, when the electrolyte membrane is produced by stretching the raw material membrane, the YI value can also be kept low by increasing the amount of exhaust air in the device when stretching the raw material membrane, or by stretching under an inert gas flow. Specifically, the YI value can be measured by transmission of an electrolyte membrane cut into a square measuring 5 cm on one side using a Spectrophotometer: SE600 manufactured by Nippon Denshoku Industries Co., Ltd., with a D65 light source. The electrolyte membrane may be 75 μm thick, or may be laminated to adjust the thickness to 75 μm. Alternatively, the YI values ​​of three membranes with different thicknesses, such as 25 μm, 50 μm, and 100 μm, may be measured, and the YI value at 75 μm may be calculated from the linear relationship between the thickness and the YI value.

[0150] (anode electrode) The anode electrode has an electrically conductive support and an anode catalyst. The support of the anode electrode is preferably 0.1 mm or more, more preferably 0.3 mm or more, from the viewpoint of increasing mechanical strength and improving handling. On the other hand, from the viewpoint of reducing the cell size, it is preferably 5.0 mm or less, more preferably 3.0 mm or less. In addition, it is preferable that the support has a mesh structure from the viewpoint of exhausting oxygen gas generated at the anode and suppressing an increase in resistance due to bubbles adhering to the surface. In addition, the anode electrode that generates oxygen gas is preferably a porous body in order to avoid an increase in resistance due to bubbles and to promote the supply of the electrolyte, and is preferably excellent in acid corrosion resistance. From this viewpoint, it is preferable that the support is made of titanium.

[0151] The anode catalyst is supported on the surface of the support of the anode electrode and is used in a state of being immersed in water or an acidic electrolyte, and a platinum group noble metal oxide catalyst is preferably used, among which an iridium oxide-based electrode catalyst material is preferred from the viewpoint of durability.

[0152] (Hydrogenated organic compound) In the catalyst layer of this embodiment, it is preferable that at least a part or all of the organic compound to be hydrogenated is an aromatic compound. Furthermore, in the catalyst layer of this embodiment, it is preferable that the aromatic compound is at least one selected from the group consisting of benzene, naphthalene, anthracene, toluene, xylene, diphenylmethane, diphenylethane, triphenylmethane, triphenylethane, dibenzyltoluene, phenol, pyridine, pyrimidine, pyrazine, quinoline, and isoquinoline. Moreover, these aromatic compounds may be contained alone or may be a mixture of two or more. Moreover, it is more preferable that the organic compound to be hydrogenated is a liquid at room temperature and normal pressure. By using a liquid as an electrolyte, electrochemical hydrogenation by an electrolytic synthesis cell is possible without using a temperature and pressure raising facility, and it also tends to be easy to handle as a hydrogen carrier. From this viewpoint, it is more preferable that the organic compound to be hydrogenated is benzene, toluene, xylene, diphenylethane, or quinoline, and toluene is most preferable. EXAMPLES

[0153] The following are specific examples. , reference example The present invention will be described with reference to examples and comparative examples, but is not limited to these.

[0154] [Thickness measurement] The thickness (mm) of the cathode diffusion layer was measured using a contact type film thickness meter (manufactured by Toyo Seiki Seisakusho, Ltd.).

[0155] [Measurement of unit weight] Cathode diffusion layer weight (g m -2 ) was calculated by dividing the mass of an electrode cut to a size of 50 x 50 mm by its area.

[0156] [Measurement of bulk density] First, the dimensions of the cathode diffusion layer are measured using a caliper or the like, and the bulk volume V of the cathode diffusion layer is calculated from the obtained dimensions. bulk Next, the mass M of the cathode diffusion layer is measured using a precision balance. The obtained mass M and bulk volume V bulk From the above, the bulk density ρ of the cathode diffusion layer is calculated using the following formula (Y). bulk (g cm -3 ) can be obtained. ρ bulk =M / V bulk (Y)

[0157] [True density measurement] True density of the cathode diffusion layer ρ real (g cm -3 ) can be determined by the sink-float method using a mixture of n-heptane, carbon tetrachloride, and ethylene dibromide. Specifically, a cathode diffusion layer of appropriate size is placed in a stoppered test tube. Next, the three solvents are mixed appropriately and added to the test tube, which is then immersed in a thermostatic bath at 30°C. If the specimen floats, n-heptane, which has a low density, is added. On the other hand, if the specimen sinks, ethylene dibromide, which has a high density, is added. This process is repeated until the specimen floats in the liquid. Finally, the density of the liquid is measured using a Gay-Lussac pycnometer.

[0158] [Calculation of void ratio] The bulk density ρ calculated as above bulk and true density ρ real From the above, the porosity V is calculated using the following formula (X): f,pore (%) can be calculated. V f,pore =((1 / ρ bulk )-(1 / ρ real )) / (1 / ρ bulk )×100(%) (X)

[0159] [Structural analysis using X-ray CT] The carbon foam was subjected to structural analysis by X-ray CT with the thickness direction as the x-axis. Specifically, in order to make it easier to take X-ray images, each of the examples was subjected to electroless copper plating, and then test pieces (samples) were taken, and structural analysis was performed on the test pieces using a high-resolution 3D X-ray microscope nano3DX (manufactured by Rigaku Corporation). The specific electroless plating conditions and X-ray CT analysis conditions are as follows. The obtained three-dimensional image was processed by a three-dimensional median filter with a filter size of a radius of two pixels at adjacent one pixel, and binarized using Otsu's algorithm. Next, using the Centerline editor (Ver. 7) of the software Simpleware manufactured by JSOL Corporation with the default settings, lines smaller than 2.16 μm were removed as noise, and the number of bonds within the measurement field of view of 300 μm × 300 μm × 300 μm, N, was calculated. n , number of linear parts N l was detected. Furthermore, the thickness direction of the carbon foam is defined as the x direction (x axis), the direction perpendicular to the x direction is defined as the y direction (y axis), and the direction perpendicular to the x direction and the y direction is defined as the z direction (z axis). The vectors of each linear portion within the measurement field of view are calculated, and the average value θ of the orientation degree of each vector relative to the x axis is calculated. avex (deg), the average degree of orientation with respect to the y-axis θ avey (deg), the average degree of orientation with respect to the z-axis θ avez The orientation angle (deg) was calculated. The orientation angle was converted to be within 90 degrees.

[0160] [Electroless plating conditions] The sample was immersed in OPC Condiclean MA (Okuno Pharmaceutical Co., Ltd., diluted with distilled water to 100 mL / L) at 70°C for 5 minutes, and then washed with distilled water for 1 minute. It was then immersed in OPC Predip 49L (Okuno Pharmaceutical Co., Ltd., diluted with distilled water to 10 mL / L, with 1.5 mL / L of 98% sulfuric acid added) at 70°C for 2 minutes, and then washed with distilled water for 1 minute. It was then immersed in a 1:1 solution of OPC Inducer 50AM (Okuno Pharmaceutical Co., Ltd., diluted with distilled water to 100 mL / L) and OPC Inducer 50CM (Okuno Pharmaceutical Co., Ltd., diluted with distilled water to 100 mL / L) at 45°C for 5 minutes, and then washed with distilled water for 1 minute. It was then immersed in OPC-150 Crysta MU (Okuno Pharmaceutical Co., Ltd., diluted with distilled water to 150 mL / L) at room temperature for 5 minutes, and then washed with distilled water for 1 minute. Next, it was immersed in OPC-BSM (Okuno Chemical Industries, diluted with distilled water to 125 mL / L) at room temperature for 5 minutes. Next, it was immersed in a solution of Chemical Copper 500A (Okuno Chemical Industries, diluted with distilled water to 250 mL / L) and Chemical Copper 500B (Okuno Chemical Industries, diluted with distilled water to 250 mL / L) mixed at a 1:1 ratio at room temperature for 10 minutes, and then washed with distilled water for 5 minutes. It was then vacuum dried at 90°C for 12 hours to remove moisture.

[0161] [X-ray conditions] X-ray target: Cu X-ray tube voltage: 40kV X-ray tube current: 30mA [Shooting conditions] Number of projections: 1500 sheets Rotation angle: 180° Exposure time: 20 seconds / frame Resolution: 1648 x 1202 pixels Pixel size: 0.54μm / pixel Observation area size: 624μm×624μm×H600μm From the above structural analysis, the number of joints N n , number of linear parts N l The average orientation angle (deg) in three mutually perpendicular directions (x, y, z) and the density of the bonds (number of bonds Nn / mm3) were determined. The results obtained are shown in Table 1. θ in Table 1 c (deg) is θ avex , θ avey , θ avez The difference between the maximum and minimum values ​​in θ d (deg) is θ avex and θ avey Or θ avez The smaller of the differences between these is obtained.

[0162] [Method of measuring average carbon frequency and average carbon area ratio] The three-dimensional images taken in the above [Structural analysis by X-ray CT] were processed by a three-dimensional median filter with a filter size of 2 pixels radius at adjacent 1 pixel, and binarized using Otsu's algorithm. Furthermore, within the analysis area (624 μm × 624 μm) of the cross-sectional image in the thickness direction of the carbon foam (cross-sectional image cut perpendicular to the thickness direction of the carbon foam), the particle analysis function of the image processing software ImageJ was used to detect the number of continuous carbon parts in the analysis area and the total area of ​​the continuous carbon parts, and the carbon frequency per 1 μm × 1 μm and the carbon area ratio per analysis area area were calculated by dividing by the area of ​​the analysis area as shown below. The same operation was repeated for 1152 cross-sectional images in the thickness direction of the carbon foam (obtained at a pitch of 0.54 μm), and the average value of the measured values ​​obtained in the entire area was calculated to obtain the average carbon frequency and average carbon area ratio. The analysis was performed under analysis conditions that included the image edge regions. In addition, to calculate the average, the cross-sectional images with a carbon area ratio of 0.01 or more in the analysis region were used to exclude regions where no carbon exists as samples. Carbon Frequency (μm -2 ) = Number of continuous carbon parts / Area of ​​analysis region Carbon area ratio = total area of ​​continuous carbon parts / area of ​​analysis region [Image processing conditions] Resolution: 1152 x 1202 pixels Pixel size: 0.54μm / pixel Thickness direction: 1152 sheets (0.54 μm / pitch) Software used: ImageJ 1.50i

[0163] [Method of measuring standard deviation of carbon frequency] The standard deviation of the carbon frequency of the above-mentioned carbon foam obtained from each cross-sectional image in the thickness direction was calculated. In order to exclude areas where carbon does not exist as a sample, cross-sectional images with a carbon area ratio of 0.01 or more in the analysis area were used.

[0164] [Method for measuring standard deviation of carbon area ratio] The standard deviation of the carbon area ratio of the above-mentioned carbon foam obtained from each cross-sectional image in the thickness direction was calculated. In order to exclude the area where no carbon exists as a sample, the calculation was performed using cross-sectional images in which the carbon area ratio in the analysis area was 0.01 or more.

[0165] [Method of measuring average fiber diameter] Average fiber diameter d of the fibrous carbon that constitutes the cathode diffusion layer ave The diameter (μm) is determined by image analysis of a scanning electron microscope image. Specifically, a carbon electrode is observed at a magnification of 10,000 times using a scanning electron microscope. The thickness of the fibrous carbon is measured at 20 random locations from the obtained observation image. Assuming that the cross-sectional shape is circular, the average thickness is taken as the average fiber diameter d ave Let us assume that.

[0166] [Carbon content] The carbon content of the cathode diffusion layer was determined by X-ray fluorescence analysis. A sample cut into 35 mm square was placed in a sample holder for an X-ray irradiation diameter of 30 mmφ, and then measured using a Rigaku Corporation ZSX-100E X-ray fluorescence analyzer (wavelength dispersive type, Rh tube). Semi-quantitative analysis of all elements was performed with an X-ray irradiation diameter of 30 mmφ, and the carbon content (wt%) of all elements was determined.

[0167] [Surface oxygen concentration] The elemental composition of the surface of the cathode diffusion layer was measured using an X-ray photoelectron spectrometer (VersaProbe II, manufactured by ULVAC-PHI, Inc.). At this time, the relative elemental concentration atomic% (hereinafter, "at%) of the main element peaks, C1s peak near 285 eV, N1s peak near 400 eV, O1s peak near 533 eV, and N1s peak near 400 eV, was calculated and calculated as a percentage. If there were any other element peaks with large detection intensity, they were also included in the calculation as a percentage.

[0168] [Evaluation of crystallite size] Example 1 5, 7~10, Reference example 6, 11~15 The crystallite size Lc (nm) was evaluated from the diffraction of the (002) plane of the cathode diffusion layer according to Comparative Examples 1 to 3. After the sample was crushed in a mortar, the crushed sample was subjected to wide-angle X-ray measurement using a tabletop X-ray diffractometer D2 PHASER (manufactured by Bluker). The specific measurement conditions are as follows: [Measurement conditions] Source: Cu Kα Tube current: 30mA Tube voltage: 40kV Slit: 1mm Sample rotation speed: 10 rpm Measurement time for one step: 0.3 sec Starting angle (2θ): 5.00° Measurement step (2θ): 0.01° End angle (2θ): 90.00° After the above measurements, the obtained data was analyzed to calculate the crystallite size Lc (nm). The crystallite size Lc can be calculated by substituting the half-width β of the diffraction peak of the (002) plane that appears near 2θ = 25 degrees and the angle θ of the peak maximum into the following Scherrer formula (c). Generally, the higher the temperature at which carbonization is performed, the higher the crystallinity and the larger the Lc value. Lc = (Kλ) / βcosθ (c) Here, K is the shape factor and λ is the wavelength of the radiation source. Since the shape factor is the (002) plane diffraction, 0.90 is substituted. Since CuKα is used as the radiation source in this study, 1.541 is substituted for the calculation. When heat-treated at a high temperature of 2000°C, the crystallinity is increased and a larger Lc is shown compared to when heat-treated at 1100°C.

[0169] [Taper bending stiffness] The Taber stiffness (gf cm) of the cathode diffusion layer was measured according to JIS P 8125-2000 using a Taber Stiffness Tester No. 2048-D manufactured by Kumagai Riki Kogyo Co., Ltd. Samples cut into strips 38 mm wide were held so that the free length was 60 mm. The bending stiffness was calculated from the average load when the strips were bent at ±15°.

[0170] [Equivalent mass] Approximately 0.02 to 0.10 g of the electrolyte membrane was immersed in 50 mL of 25°C saturated NaCl aqueous solution (0.26 g / mL), and left for 30 minutes while stirring. After that, neutralization titration was performed using 0.01N sodium hydroxide aqueous solution (Wako Pure Chemical Industries, Ltd., special grade reagent) with phenolphthalein (Wako Pure Chemical Industries, Ltd., special grade reagent) as an indicator. The Na-type ion exchange membrane obtained after neutralization was rinsed with pure water, vacuum dried and weighed. The equivalent of sodium hydroxide required for neutralization was M (mmol), and the mass of the Na-type ion exchange membrane was W (mg), and the equivalent mass EW (g / equivalent) was calculated from the following formula. Equivalent mass EW=(W / M)-22 After repeating the above procedure five times, the maximum and minimum values ​​of the five calculated EW values ​​were excluded, and the three values ​​were averaged to obtain the measurement results.

[0171] [Film thickness after stretching] The stretched electrolyte membrane was left to stand in a thermostatic chamber at 23° C. and a relative humidity of 65% for 12 hours or more, and then the membrane thickness (μm) after stretching was measured using a contact type membrane thickness meter (manufactured by Toyo Seiki Seisakusho, Ltd.).

[0172] [Craze area ratio] The craze area ratio was determined from visible light transmittance mapping measured using an optical microscope equipped with an automatic stage that can move in any X-axis direction and a Y-axis direction perpendicular to the X-axis, and a visible light spectrophotometer "uSight-2000" (product name, manufactured by Technospex). Light focused to a diameter of 1 μm was moved at 1 μm step intervals to map the visible light transmittance of the stretched film in an area of ​​75 mm length x 50 mm width. The wavelength range of the visible light measured was 450-700 nm. The ratio of the area of ​​the area with a transmittance of 10% or less to the total area mapped was taken as the craze area ratio (%).

[0173] [Flatness] The flatness of the electrolyte membrane was evaluated based on the ratio of the length along the membrane surface to the membrane's projected dimensions. The length along the membrane surface was determined from the height-position profile of the membrane surface measured using a scanning microscope. Specifically, the height of the membrane surface of a membrane cut into a square of approximately 140 mm square was measured at 25 points at 5 mm intervals in the X-axis direction. The height-position profile of the membrane surface was approximated by a spline function, and the length along the membrane surface was calculated by numerical calculation. The flatness index was calculated using the following formula and evaluated according to the following criteria. Flatness index = Length along the membrane surface / Projected dimension of membrane A: Less than 1.05 B: 1.05 or more and less than 1.1 C: 1.1 or more and less than 1.2 D:1.2 or more

[0174] [Ion cluster diameter] The ion cluster diameter (nm) was measured by small-angle X-ray scattering (SAXS). The electrolyte membrane was immersed in water at 25°C for 24 hours, and while immersed in water, point-focused X-rays were irradiated from the membrane surface and the direction perpendicular to the membrane surface to detect the transmitted scattered light. A small-angle X-ray scattering measuring device "Nano Viewer" (manufactured by Rigaku Corporation) was used for the measurement. In the small-angle region, a detector "PILATUS100K" (manufactured by Rigaku Corporation) was used with a sample-to-detector distance of 841 mm, and in the wide-angle region, a sample-to-detector distance of 75 mm was used with an imaging plate as the detector. By combining both profiles, scattering data was obtained in the scattering angle range of 0.1°<scattering angle (2θ)<30°.

[0175] The measurements were performed with seven samples stacked, and the exposure time was 15 minutes for both the small-angle and wide-angle measurements. When data was obtained using a two-dimensional detector, the data was converted to one-dimensional data using a reasonable method such as circular averaging. The obtained SAXS profile was subjected to corrections due to the detector, such as dark current correction, and correction for scattering by materials other than the sample (empty cell scattering correction). When the influence of the X-ray beam shape on the SAXS profile (influence of smear) was large, correction for the X-ray beam shape (desmear) was also performed. From the one-dimensional SAXS profile thus obtained, the ion cluster diameter was calculated according to the method described in Yasuhiro Hashimoto, Naoki Sakamoto, and Hideki Iijima, Polymer Research Vol. 63 No. 3 pp. 166 2006. That is, it was assumed that the ion cluster structure is represented by core-shell type hard spheres with a particle size distribution, and the average cluster diameter (ion cluster diameter) and ion cluster number density were calculated by fitting the SAXS profile in the scattering angle region where scattering from ion clusters is dominant in the measured SAXS profile using a theoretical scattering equation based on this model. In this model, the core corresponds to the ion cluster, and the diameter of the core is the ion cluster diameter. The shell layer is virtual, and the electron density of the shell layer is the same as that of the matrix part. The shell layer thickness is set to 0.25 nm. The theoretical scattering formula of the model used for fitting is shown in the following formula (A). The fitting range is set to 1.4<2θ<6.7°.

number

[0176] [Orientation parameters] The in-plane orientation parameter and out-of-plane orientation parameter of the electrolyte membrane were determined by approximating the azimuthal intensity distribution I(φ) of the peak derived from the ion cluster in the two-dimensional small-angle scattering measured according to the above-mentioned method, using the orientation function shown in the following formula.

number

[0177] [Crystal long period] The crystal long period (nm) is the scattering vector of 0.1 to 1.0 nm in the one-dimensional SAXS profile obtained according to the above method. -1 The Bragg equation was used to determine the position of the peak resulting from the periodicity of the electron density difference between the crystal and amorphous regions, which occurs in the range of . On the other hand, the peak intensity was defined as the ratio of the difference between the peak top intensity and the baseline intensity to the baseline intensity. If no peak was detected, the difference in intensity was not detectable and was recorded as "-".

[0178] [Dimensional change rate due to immersion in 2M sulfuric acid solution] The electrolyte membrane was dried at 50°C or less under reduced pressure for 2 hours, and the moisture content was adjusted to 1% by mass or less. The membrane was then cut into a square of 7 cm on each side to prepare a test electrolyte membrane. The test electrolyte membrane was immersed in a 2M aqueous sulfuric acid solution at 25°C for 30 minutes. The dimensions of the test electrolyte membrane in the X and Y directions after immersion were measured using a reading microscope "D2XY-KSH" (product name, manufactured by Nippon Koki Seisakusho Co., Ltd.), and the dimensional change rate was calculated using the following formula. The X direction is a direction arbitrarily selected on the membrane surface, and the Y direction is a direction perpendicular to the X direction on the membrane surface. Dimensional change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)} x 100

[0179] [Dimensional change rate due to immersion in distilled water] The electrolyte membrane was dried at 50°C or less under reduced pressure for 2 hours, and the moisture content was adjusted to 1% or less. The membrane was then cut into a square of 7 cm on each side to prepare a test electrolyte membrane. The test electrolyte membrane was immersed in distilled water at 25°C for 30 minutes. The dimensions of the test electrolyte membrane in the X, Y, and Z directions after immersion were measured using a reading microscope "D2XY-KSH" (product name, manufactured by Nippon Kogyo Seisakusho Co., Ltd.), and the dimensional change rate was calculated using the following formula. The X direction is a direction arbitrarily selected on the membrane surface, and the Y direction means a direction perpendicular to the X direction on the membrane surface. The Z direction means a direction perpendicular to the X and Y directions. Dimensional change rate (%) = {(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)} x 100

[0180] [Puncture strength] The puncture strength was measured using a puncture tester "Puncture Strength Tester SPK-NDA1-A" (product name, manufactured by Kato Tech Co., Ltd.) for electrolyte membranes that had been left at room temperature for 12 hours or more. The electrolyte membrane was sandwiched between two metal plates with a circular hole of 10 mm in diameter, and pierced at a speed of 2 mm / sec with a needle of 0.5 mm radius of curvature. The puncture strength (kgf / μm) was calculated by dividing the maximum load (kgf) on the load-displacement curve by the thickness (μm) of the electrolyte membrane.

[0181] [YI value measurement] The YI value of the electrolyte membrane was measured by transmission using a D65 light source with a Spectrophotometer: SE600 manufactured by Nippon Denshoku Industries Co., Ltd. The electrolyte membrane used was 75 μm thick and cut into a square with a side of 5 cm.

[0182] [Perfluorocarbon polymer] In this example, perfluorocarbon polymers having the following two types of structures were used. A perfluorocarbon polymer having a structure represented by the following formula (P1): - [CF 2 CF 2 ]―[CF 2 -CF(-O-CF 2 CF 2 -SO 3 H)]- (P1) A perfluorocarbon polymer having a structure represented by the following formula (P2): - [CF 2 CF 2 ]―[CF 2 -CF(-O-CF 2 CFCF 3 -O-CF 2 CF 2 -SO 3 H)]- (P2)

[0183] Example 1 The cathode diffusion layer was made of carbon foam produced by carbonizing BASF's melamine resin foam BASOTECT G+. A 6 mm thick carbon fiber nonwoven fabric was placed on the melamine resin foam (dimensions: 90 mm x 120 mm x 25 mm), and a graphite plate was placed on top of it. A compressive load of 280 Pa was applied, and the melamine resin foam was introduced into a heat treatment furnace while this compressive load was applied. Next, nitrogen gas was supplied into the furnace at a flow rate of 2.5 L / min, and the temperature in the furnace was raised to 1100°C at a heating rate of 5°C / min, and then the temperature was maintained for 1 hour to carbonize the melamine resin foam. After that, the temperature in the furnace was lowered to room temperature, and the carbonized melamine resin foam was taken out of the furnace. The obtained cathode diffusion layer (carbon foam) was made of continuous voids, and had a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where the linear parts were bonded. For the electrolyte membrane, a 75 μm-thick membrane made of a perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 750 g / eq) was used, which was immersed in distilled water at 70°C for 30 minutes, washed four times, and then dried at 100°C for 20 minutes without being stretched. The toluene electrolytic hydrogenation test was carried out using an electrolytic cell manufactured by Miklab, with an electrode area of ​​2 x 2 cm. The cathode and anode plates were formed with parallel flow paths for the circulation of sulfuric acid and toluene, respectively, and their surfaces were gold-plated to suppress corrosion due to electrolysis. The cell was also designed to allow the insertion of a rod-shaped heater to control the cell temperature. The components that make up the cell were layered in the following order from the cathode side, and the cell was assembled by tightening the bolts to the specified torque. Cathode plate / carbon foam / cathode catalyst layer-membrane assembly / anode catalyst electrode / anode diffusion layer / anode plate The anode catalyst electrode and the anode diffusion layer were respectively a commercially available oxygen evolution electrode (titanium electrode coated with iridium oxide catalyst) and titanium fiber sintered body 2GDL5-030 (thickness 300 μm) manufactured by Bekaert Toko Metal Fiber Co., Ltd. The thickness of the gasket used between the cathode plate and the membrane was adjusted so that the thickness of the carbon foam when assembled into the cell would be 250 μm. The cathode catalyst layer-membrane assembly was prepared by a decal method in which the cathode catalyst layer prepared by spray coating and the membrane were bonded by hot pressing. First, 0.50 g of platinum-ruthenium supported carbon catalyst particles (Tanaka Kikinzoku Kogyo Co., Ltd., standard catalyst for solid polymer fuel cells, carbon monoxide poisoning resistant catalyst standard TEC 61E54-Pt and Ru content 54 mass% (Pt:Ru = 1: 1.5) supported catalyst (support Ketjenblack EC), hereinafter referred to as "Pt / Ru-C catalyst"), 2.00 g of distilled water, and 5.00 g of Sigma-Aldrich Nafion 117 solution (concentration 5 wt%) were placed in a zirconia pot and mixed with a planetary ball mill to prepare a cathode catalyst ink. Next, the cathode catalyst ink was applied to a Teflon (registered trademark) sheet with a basis weight of 0.5 mg cm using a small spray coating device AV-8 type manufactured by Acing Technologies Co., Ltd. -2 Finally, the membrane and the cathode catalyst layer were hot pressed at 140° C. for 2 minutes, and the Teflon (registered trademark) sheet substrate was then peeled off to produce a cathode catalyst layer-membrane assembly. [Electrolytic test] The electrolysis test was carried out on the electrolysis cell assembled according to the above procedure. First, 1M H 2 SO 4 and 100% toluene at a flow rate of 2 ml min -1 Next, the cell was heated to 60°C and then a current density of 0.1 Acm was applied. -2 The cell was aged by passing a constant current of 0.1 A cm for 2 h. Then, the current density was reduced to 0.1 A cm. -2 Width: 0.5Acm -2 was increased to. Current density 0.5Acm -2 The voltage efficiency (%) was calculated as the ratio of the thermoneutral voltage of 1.138 V for the electrolytic hydrogenation of toluene to the cell voltage at 0.2 V. On the other hand, the current efficiency (%) was determined by quantitatively measuring the methylcyclohexane concentration in toluene at the cathode after electrolysis at a predetermined current density for a certain period of time, using gas chromatography. Then, the energy efficiency (%), which is the product of the voltage efficiency (%) and the current efficiency (%), was also calculated. FIG. 3 is an SEM image of the carbon foam used in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0184] Example 2 A carbon foam was produced in the same manner as in Example 1, except that the thickness of the raw material melamine resin foam was 4 mm, and the compressive load applied to the melamine foam during carbonization was 70 Pa. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where these were bonded. The other methods for producing the membrane and the electrolytic test were also the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0185] Example 3 A carbon foam was produced in the same manner as in Example 1, except that the thickness of the raw material melamine resin foam was 30 mm, and the compressive load applied to the melamine foam during carbonization was 630 Pa. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where these were bonded. The other methods for producing the membrane and the electrolytic test were also the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0186] Example 4 A carbon foam was produced in the same manner as in Example 1, except that the carbonization temperature was 2000°C. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of about 2 μm and joints where these were joined. The film production method and electrolytic test method were also the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0187] Example 5 A carbon foam was produced in the same manner as in Example 1, except that the thickness of the raw material melamine resin foam was 3 mm, the compressive load applied to the melamine foam during carbonization was 70 Pa, and the carbonization temperature was 2000°C. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where these were bonded. The film production method and electrolytic test method were also the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0188] ( reference Example 6) A carbon foam was produced in the same manner as in Example 1, except that the thickness of the raw material melamine resin foam was 2 mm, the compressive load applied to the melamine foam during carbonization was 18 Pa, and the carbonization temperature was 1500°C. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where these were bonded. The film production method and electrolytic test method were also the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0189] Example 7 The raw material melamine resin foam (dimensions: 90 mm x 120 mm x 40 mm) was placed on a 250 mm square graphite plate, a 150 mm x 20 mm SUS plate with a thickness of 0.5 mm was placed next to the sample as a spacer, and a graphite plate was placed on top to sandwich the sample and the spacer. The sample was sandwiched between the graphite plates and introduced into a vacuum press (KVHC-II) manufactured by Kitagawa Seiki Co., Ltd., and pressed at a set pressure of 2.0 MPa while vacuuming with a vacuum pump. The sample was heated to 360°C at a heating rate of 5°C / min while continuing to reduce the pressure, and then cooled after being held for 10 minutes. After removing the sample, a graphite plate was placed on the sample again in the same manner as in Example 6, a compressive load of 18 Pa was applied, and the sample was introduced into a heat treatment furnace with this compressive load applied, and heat-treated at 1500°C to produce a carbon foam according to Example 7. The carbon foam obtained had continuous voids and a structure consisting of linear parts with a fiber diameter of about 2 μm and bonded parts where these were bonded. The method for producing the membrane and the method for the electrolytic test were the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0190] Example 8 A 300 μm thick raw membrane made of a perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 950 g / eq) was immersed in distilled water at 70 ° C for 30 minutes, washed four times, and dried at 100 ° C for 20 minutes. The membrane was stretched by simultaneous biaxial stretching using a batch-type biaxial stretching machine "IMC-1AA6" (product name, manufactured by Imoto Manufacturing Co., Ltd.). The raw membrane cut to 92.5 mm in both the orthogonal X and Y directions was held in the stretching machine so that the chuck interval in the X and Y directions was 72.5 mm. When 3 min had elapsed after the temperature of the heating chamber of the stretching machine reached 140 ° C, simultaneous biaxial stretching was started at a stretching speed of 100 mm / min. When the chuck interval in the X and Y directions reached 145 mm, the stretching was stopped, and the heating chamber was immediately opened and cooling was started while the membrane was held by the chuck. At the same time, the chuck gap was narrowed by 0.7 mm so that the relaxation rate in the X and Y directions was 0.5%. After the membrane was cooled to room temperature, it was removed from the chuck to obtain a biaxially stretched electrolyte membrane with a stretch ratio of 2.0 in the X and Y directions. The carbon foam preparation method and the electrolysis test method were the same as those in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0191] Example 9 A 470 μm thick raw membrane made of a perfluorocarbon polymer (polymer structure: formula (P2), equivalent mass EW = 1100 g / eq) was immersed in distilled water at 70 ° C for 30 minutes, washed four times, and dried at 100 ° C for 20 minutes, and then biaxially stretched. The raw membrane cut to 78 mm in both the orthogonal X and Y directions was held in a stretching machine so that the chuck interval in the X and Y directions was 58 mm. When 3 minutes had elapsed after the temperature of the heating chamber of the stretching machine reached 100 ° C, simultaneous biaxial stretching was started at a stretching speed of 100 mm / min. When the chuck interval in the X and Y directions reached 145 mm, the stretching was stopped, and the heating chamber was immediately opened with the membrane held by the chuck to start cooling. At the same time, the chuck interval was narrowed by 0.7 mm so that the relaxation rate in the X and Y directions was 0.5%. After the membrane was cooled to room temperature, it was removed from the chuck to obtain a biaxially stretched electrolyte membrane with a stretch ratio of 2.5 in the X and Y directions. The carbon foam preparation method and the electrolytic test method were the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0192] Example 10 A 630 μm thick raw membrane made of a perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 950 g / eq) was immersed in distilled water at 70 ° C for 30 minutes, washed four times, and dried at 100 ° C for 20 minutes, and then biaxially stretched. The raw membrane cut to 70 mm in both the orthogonal X and Y directions was held in a stretching machine so that the chuck interval in the X and Y directions was 50 mm. When 3 minutes had elapsed after the temperature of the heating chamber of the stretching machine reached 140 ° C, simultaneous biaxial stretching was started at a stretching speed of 100 mm / min. When the chuck interval in the X and Y directions reached 145 mm, the stretching was stopped, and the heating chamber was immediately opened with the membrane held by the chuck to start cooling. At the same time, the chuck interval was narrowed by 1.4 mm so that the relaxation rate in the X and Y directions was 1.0%. After the membrane was cooled to room temperature, it was heated again at 140° C. for 5 min with the chuck gap still open. After the membrane was cooled to room temperature, it was removed from the chuck to obtain a heat-set biaxially stretched electrolyte membrane with a stretch ratio of 2.9 in the X and Y directions. The carbon foam was prepared by the same method as in Example 1, and the electrolysis test was performed by the same method. The conditions of this example are as shown in Tables 1 to 3.

[0193] ( reference Example 11) A carbon foam was produced in the same manner as in Example 1, except that the thickness of the raw material melamine resin foam was 2 mm, and no load was applied to the melamine foam during carbonization. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where these were bonded. The other methods for producing the membrane and the electrolytic test were also the same as in Example 1. The bulk density of the obtained carbon foam was 0.006 gcm -3 Although this was a small value, sufficient electrical contact and conduction could be obtained by compressing a 1,000 μm thick carbon foam to 250 μm and incorporating it into a cell. The conditions of this example are as shown in Tables 1 to 3.

[0194] ( reference Example 12) A carbon foam was produced in the same manner as in Example 1, except that the thickness of the raw material melamine resin foam was 2 mm, no load was applied to the melamine foam during carbonization, and the carbonization temperature was 2000°C. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 2 μm and bonded parts where these were bonded. The film production method and electrolytic test method were also the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0195] ( reference Example 13) The cathode diffusion layer was made of carbon fiber paper (SIGRACET GDL39AA) manufactured by SGL CARBON. Meanwhile, the membrane was the same biaxially stretched membrane as in Example 8. The other electrolysis test methods were the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0196] ( reference Example 14) Carbon fiber paper (SIGRACET GDL39AA) manufactured by SGL CARBON was used for the cathode diffusion layer. On the other hand, for the membrane, a raw material membrane with a thickness of 300 μm made of perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 950 g / eq) was immersed in distilled water at 70 ° C for 30 minutes, washed twice, and dried at 100 ° C for 20 minutes. The membrane was stretched by simultaneous biaxial stretching using a batch-type biaxial stretching machine "IMC-1AA6" (product name, manufactured by Imoto Manufacturing Co., Ltd.). The raw material membrane cut to 92.5 mm in both the orthogonal X and Y directions was held by the stretching machine so that the chuck interval in the X and Y directions was 72.5 mm. After 3 minutes had elapsed after the temperature of the heating chamber of the stretching machine reached 140 ° C, simultaneous biaxial stretching was started at a stretching speed of 25 mm / min. When the chuck intervals in the X and Y directions reached 145 mm, the stretching was stopped, and the heating chamber was immediately opened with the membrane held by the chucks to start cooling. At the same time, the chuck interval was narrowed by 0.7 mm so that the relaxation rates in the X and Y directions were 0.5%. When the membrane was cooled to room temperature, it was removed from the chucks to obtain a biaxially stretched electrolyte membrane with a stretch ratio of 2.0 in the X and Y directions. The other electrolysis test methods were the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0197] ( reference Example 15) Carbon fiber paper (SIGRACET GDL39AA) manufactured by SGL CARBON was used for the cathode diffusion layer. On the other hand, for the membrane, a raw material membrane with a thickness of 300 μm made of perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 950 g / eq) was stretched by simultaneous biaxial stretching using a batch-type biaxial stretching machine "IMC-1AA6" (product name, manufactured by Imoto Manufacturing Co., Ltd.) without washing with distilled water. At that time, the inside of the heating chamber during stretching was evacuated from the sealed state at 50 L / sec. The raw material membrane cut to 92.5 mm in both the orthogonal X and Y directions was held by the stretching machine so that the chuck interval in the X and Y directions was 72.5 mm. After 3 min had elapsed after the temperature of the heating chamber of the stretching machine reached 140 °C, simultaneous biaxial stretching was started at a stretching speed of 100 mm / min. When the chuck intervals in the X and Y directions reached 145 mm, the stretching was stopped, and the heating chamber was immediately opened with the membrane held by the chucks to start cooling. At the same time, the chuck interval was narrowed by 0.7 mm so that the relaxation rates in the X and Y directions were 0.5%. When the membrane was cooled to room temperature, it was removed from the chucks to obtain a biaxially stretched electrolyte membrane with a stretch ratio of 2.0 in the X and Y directions. The other electrolysis test methods were the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0198] Comparative Example 1 The cathode diffusion layer was made of carbon fiber paper (SIGRACET GDL39AA) manufactured by SGL CARBON. The other membrane preparation methods and electrolysis test methods were the same as those in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0199] Comparative Example 2 A carbon fiber nonwoven fabric (SIGRACELL GFD4.6EA) manufactured by SGL CARBON was used for the cathode diffusion layer. A Teflon (registered trademark) plate was placed between the cathode plate and the membrane to adjust the thickness of the carbon fiber nonwoven fabric to 3 mm when assembled into the cell. The other membrane fabrication methods and electrolysis test methods were the same as in Example 1. The carbon fiber nonwoven fabric was significantly thicker than the carbon foam and carbon fiber paper, so the taber bending stiffness could not be measured correctly. The conditions of this example are as shown in Tables 1 to 3.

[0200] Comparative Example 3 For the cathode diffusion layer, a carbon foam was used, which was obtained by carbonizing polyimide foam SOLIMIDE manufactured by Boyd Corp. at 1100°C in the same manner as in Example 1. As can be seen from the scanning electron microscope image shown in Figure 4, this carbon foam did not have a structure consisting of linear parts and joints, but had a so-called house of cards structure in which wavy carbon thin films were layered on top of each other. The other methods for preparing the membrane and the electrolysis test were the same as in Example 1. FIG. 4 is an SEM image of the carbon foam used in Comparative Example 3. The conditions of this example are as shown in Tables 1 to 3.

[0201] Comparative Example 4 A melamine resin foam BASOTECT G+ manufactured by BASF was immersed in 2M sulfuric acid at room temperature and left to stand for one week. It was then washed with distilled water, and it was confirmed that the washing liquid became neutral. Thereafter, a carbon foam was produced in the same manner as in Example 1. The obtained carbon foam had continuous voids and a structure consisting of linear parts with a fiber diameter of approximately 0.4 μm and joints where these were joined, but it was very weak in strength and could not be incorporated into an electrolysis cell. The conditions of this example are as shown in Tables 1 to 3.

[0202] Comparative Example 5 Carbon fiber paper (SIGRACET GDL39AA) manufactured by SGL CARBON was used for the cathode diffusion layer. On the other hand, for the membrane, a raw material membrane with a thickness of 300 μm made of perfluorocarbon polymer (polymer structure: formula (P1), equivalent mass EW = 950 g / eq) was stretched by simultaneous biaxial stretching using a batch-type biaxial stretching machine "IMC-1AA6" (product name, manufactured by Imoto Manufacturing Co., Ltd.) without performing a washing operation with distilled water. The raw material membrane cut to 92.5 mm in both the orthogonal X direction and Y direction was held in the stretching machine so that the chuck interval in the X direction and Y direction was 72.5 mm. When 3 min had elapsed after the temperature of the heating chamber of the stretching machine reached 140 ° C., simultaneous biaxial stretching was started at a stretching speed of 100 mm / min. When the chuck interval in the X direction and Y direction reached 145 mm, the stretching was stopped, and the heating chamber was immediately opened and cooling was started while the membrane was held by the chuck. At the same time, the chuck gap was narrowed by 0.7 mm so that the relaxation rates in the X and Y directions were 0.5%. After the membrane was cooled to room temperature, it was removed from the chuck to obtain a biaxially stretched electrolyte membrane with a stretch ratio of 2.0 in the X and Y directions. The other electrolysis test methods were the same as in Example 1. The conditions of this example are as shown in Tables 1 to 3.

[0203] [Table 1]

[0204] [Table 2]

[0205] [Table 3]

Claims

1. A cathode diffusion layer for organic hydride production, comprising a carbon foam which is a porous body having continuous voids, has linear portions and bonding portions bonding the linear portions, the linear portions having an average fiber diameter of 0.5 μm or more and 4.0 μm or less, and has an average carbon frequency of 0.0004 to 0.0035 μm −2 .

2. 2. The cathode diffusion layer for producing an organic hydride according to claim 1, wherein the carbon foam has a Taber stiffness of 1.0 to 50.0 gf·cm as measured in accordance with JIS P8125.

3. The carbon foam has a density of the bonds of 20,000 bonds / mm 3 3. The cathode diffusion layer for producing an organic hydride according to claim 1 or 2, wherein the crystallite size is 1.50 nm or more based on diffraction of the (002) plane in powder X-ray diffraction measurement.

4. 2. The cathode diffusion layer for organic hydride production according to claim 1, wherein the carbon foam has a standard deviation of carbon frequency of 0.0005 or less.

5. 5. The cathode diffusion layer for producing an organic hydride according to claim 1, wherein the carbon foam has an average carbon area ratio of 0.010 to 0.

300.

6. 6. The cathode diffusion layer for organic hydride production according to claim 5, wherein the carbon foam has a standard deviation of carbon area ratio of 0.030 or less.

7. 13. An electrolysis cell for producing organic hydrides, comprising: a proton-conductive solid polymer electrolyte membrane; an anode catalyst layer that oxidizes water to generate protons, provided on one surface of the solid polymer electrolyte membrane; a cathode catalyst layer that reduces a substance to be hydrided, provided on the other surface of the solid polymer electrolyte membrane; and the cathode diffusion layer according to claim 1.

8. 6. An electrolysis cell for producing organic hydrides, comprising: a proton-conductive solid polymer electrolyte membrane; an anode catalyst layer that oxidizes water to generate protons, provided on one surface of the solid polymer electrolyte membrane; a cathode catalyst layer that reduces a substance to be hydrided, provided on the other surface of the solid polymer electrolyte membrane; and the cathode diffusion layer according to claim 5.

9. 8. The electrolysis cell for producing organic hydride according to claim 7, wherein the solid polymer electrolyte membrane is a perfluorocarbon polymer having an ion exchange group, the equivalent mass EW of the ion exchange group is 600 g / eq or more and 2000 g / eq or less, and the dimensional change rate in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change rate in the Z direction is 115% or more, in the dimensional change rate due to immersion in distilled water described below, and the ion cluster diameter in the direction perpendicular to the membrane surface measured by small angle X-ray scattering is 3.0 nm or more. <Dimensional change rate due to immersion in distilled water> A test electrolyte membrane having a water content of 1% or less is prepared, and the test electrolyte membrane is immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates of the test electrolyte membrane in the X direction, the Y direction perpendicular to the X direction, and the Z direction perpendicular to the X direction and the Y direction are calculated. Dimensional change rate (%)=(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)×100

10. 9. The electrolysis cell for producing organic hydride according to claim 8, wherein the solid polymer electrolyte membrane is a perfluorocarbon polymer having an ion exchange group, the equivalent mass EW of the ion exchange group is 600 g / eq or more and 2000 g / eq or less, and the dimensional change rate in at least one of the X direction and the Y direction is 80% or more and less than 100%, and the dimensional change rate in the Z direction is 115% or more, in the dimensional change rate due to immersion in distilled water described below, and the ion cluster diameter in the direction perpendicular to the membrane surface measured by small angle X-ray scattering is 3.0 nm or more. <Dimensional change rate due to immersion in distilled water> A test electrolyte membrane having a water content of 1% or less is prepared, and the test electrolyte membrane is immersed in distilled water at 25° C. for 30 minutes. The dimensional change rates of the test electrolyte membrane in the X direction, the Y direction perpendicular to the X direction, and the Z direction perpendicular to the X direction and the Y direction are calculated. Dimensional change rate (%)=(dimension in a specific direction after immersion) / (dimension in a specific direction before immersion)×100

11. 11. The electrolytic cell for producing an organic hydride according to claim 9 or 10, wherein the solid polymer electrolyte membrane has a peak intensity of a crystal long period of 0.5 or less as measured by small angle X-ray scattering.

12. 11. The electrolytic cell for producing an organic hydride according to claim 9 or 10, wherein the solid polymer electrolyte membrane has a craze area ratio of 1.5% or less.

13. 12. The electrolytic cell for producing an organic hydride according to claim 11, wherein the solid polymer electrolyte membrane has a craze area ratio of 1.5% or less.

Citation Information

Patent Citations

  • Chemical power generation / Device for manufacturing organic hydride and chemical power generation / manufacturing method for organic hydride

    JP2003045449A

  • Hydrogen storage and release apparatus

    JP2005126288A

  • Longitudinal material arranging and mounting apparatus

    JP2013111585A

  • Separator for electrolytic cells, electrolytic cell, electrochemical reduction device, and method for producing hydrogenated body of aromatic hydrocarbon compound

    JP2017179601A

  • Catalyst layer, cathode, electrolytic synthesis cell, membrane electrode assembly, organic compound hydrogenating device and method for producing hydrogenated organic compound

    JP2017190486A